Ozone critical levels to protect tree growth in the United States - Emmi Felker-Quinn; Jeffrey D. Herrick; Kemen Austin; Gray Martin; Marwa Salem; Jennifer Phelan; Christopher M. Clark (Forest Ecology and Management, 2026)

Starch modification and protein complexation synergistically strengthen hydrocolloid networks and limit enzymatic hydrolysis in gluten-free noodles - Babatunde Olawoye; Oladapo Fisoye Fagbohun; Folasade Olabimpe Adeboyejo; Boluwatife Martins Okedepo; Gladys Damilola Obalowo; Christopher Olayinka Adedoyin; Omototade Richard Ogunremi; Folasade O. Afolabi; Oseni Peter Kadiri (Food Hydrocolloids, 2026)

Nature's treasure factory: Geochemical controls on ultra-high-grade orogenic gold deposit formation - Rory R. McNab; Joël Brugger; Christopher R. Voisey; Nicolas Thebaud; Andrew G. Tomkins; Lauri T. Virnes; Laura Petrella; Denis Fougerouse; Laure Martin; Nicolas Mériaud (Earth-Science Reviews, 2026)

Challenges in the determination of 210Pb in oil scale - Christopher Martin; Kayla Cockerline; Sheldon Landsberger (Journal of Environmental Radioactivity, 2026)

Framing of ultra-processed foods in UK news media (2022–2023) and associations with quoted actors’ interests: a mixed-methods study - Jennie C Parnham; Kiara Chang; Michael Essman; Deb Smith; Mike P Etkind; Maisie McKenzie; Prisha Shah; Milica Vasiljevic; Mark Petticrew; Martin White; Anthony A Laverty; Emma Boyland; et al. (Food Policy, 2026)

PFAS in Australian raptor species: terrestrial biomonitors of environmental contamination in changing ecosystems - Phoebe Lewis; Christopher P. Johnstone; Timothy Chaston; Jordan O. Hampton; Judy Clarke; John Leeder; Yan Wang; Matthew Etterson; Jennifer Martin; Minna Saaristo (Environmental Pollution, 2026)

A standardised approach towards selecting forests for strict protection in Germany - Patricia Borel; Jan-Geert Bliefernicht; Eva Flinkerbusch; Martin Gutsch; Anke Höltermann; Ulrich Matthes; Mats Nieberg; Tobias Nowakowski; Max Tölle; Christopher P. O. Reyer (Regional Environmental Change, 2026)
Forests serve as key ecosystems for biodiversity conservation and climate change mitigation. The achievement of ambitious biodiversity targets, such as the EU Biodiversity Strategy’s target of strictly protecting 10% of the EU’s land area, requires the systematic identification of key forest areas for protection. However, clear guidance on selecting such forests is lacking. In this study, we address this issue by developing forest protection scenarios based on different conservation criteria and data from the third German National Forest Inventory. We used state-of-the-art indicators capturing different aspects of biodiversity: forest structure, habitat conservation, legal protection status, and the presence of old forests, alongside sociopolitical considerations including public ownership and equal distribution across federal states. Using a standardised, multi-criteria approach, we systematically identified forest areas for strict protection that best complied with each scenario’s criteria. Each scenario was then tested against three targets: strictly protecting 5%, 10%, and 30% of the total forest area. Our analysis revealed that, despite the application of different selection criteria in each scenario, the characteristics of the forests ultimately selected showed only moderate differences. Achieving higher protection targets, such as 10% or 30%, required including stands with lower conservation value, as evidenced by lower criterion overlap within selected forest areas. Although existing forest habitat types with no or minimal management requirements (i.e. 15.24% of German forest area) could theoretically serve as the selection pool for the 5% and 10% targets, sociopolitical considerations, such as having an equal spread of protected areas across federal states, required the incorporation of other forest areas. Overall, our findings provide a foundation for implementing Germany’s and the EU’s strict nature protection targets and demonstrate that multiple pathways exist to achieve them. However, strategic compromises may be required as the goals become more ambitious.

Marine migration influences mercury accumulation in anadromous Arctic char ( Salvelinus alpinus ) - Isabel R. Hilgendag; Michael Power; Mehdi M. Aqdam; Christopher W. Lewis; Zoya Martin; Ashley D. Ehrman; Heidi K. Swanson (Journal of Fish Biology, 2026)
Mercury (Hg) is a globally distributed toxic metal present in northern natural environments that biomagnifies in food webs and bioaccumulates in apex predator fish, such as Arctic char ( Salvelinus alpinus )—an iteroparous species with a circumpolar distribution. Arctic char exhibit a variety of life history types, with the migrating, anadromous life‐history type supporting many subsistence and small‐scale commercial fisheries in the Arctic and sub‐Arctic. Despite anadromous Arctic char having generally lower Hg concentrations than non‐anadromous conspecifics, the mechanisms that contribute to significant inter‐individual differences within this life‐history group have not been well investigated. A total of 119 anadromous Arctic char were captured from inner Frobisher Bay on Baffin Island near Iqaluit, Nunavut, in 2018 and 2019, to investigate causes of inter‐individual differences in Hg concentrations in the anadromous life‐history type of Arctic char. As hypothesized, Hg concentrations significantly decreased with increasing marine prey reliance; marine prey reliance—quantified using δ 34 S ratios—explained 93% of the variability in Hg. Arctic char that relied more on marine (vs freshwater) prey had lower Hg concentrations. Delta 34 S ratios and average somatic growth rate (size‐at‐age) were the best predictors of Hg concentrations among the set of biological variables assessed, and both were negatively related to Hg concentrations in common age groups (i.e., ages 9–13). For samples that had migration data available, Hg concentration increased with age‐at‐first migration ( R 2 = 0.32) and decreased with number of marine migrations ( R 2 = 0.57), suggesting that plasticity in life history tactics affects Hg concentrations in anadromous Arctic char. Overall, results indicate that differences in habitat use and feeding environment (i.e., freshwater vs. marine) play a significant role in determining Hg bioaccumulation in anadromous Arctic char.

Contrasting long-range transport signals of metropolitan PM2.5 in South Korea detected by SPARTAN observations - Sujin Eom; Min Ju Yeo; Donghee Lee; Ja-Ho Koo; Jhoon Kim; Yuxuan Ren; Christopher R. Oxford; Xuan Liu; Ann M. Dillner; Randall V. Martin; Sung-Deuk Choi; Chang-Keun Song; et al. (Atmospheric Pollution Research, 2026)

When everything is violence, nothing is violence: Response to Koot et al. (2025) - Fergus O'Leary Simpson; Lorenzo Pellegrini; Olajide Akinleye‐Martins; Leif Brottem; Elie Lunanga; Christopher Day; Elias Maombi Ndatabaye; Lara Collart; Naziru Zakari Muhammad; Marijke Verpoorten; Helen Kopnina; Richard Sufo (Conservation Biology, 2026)

Comparative toxicity of bisphenol A and analogues to the marine polychaete Arenicola marina: Another case of regrettable substitutes? - Paula Milliken; Anais Ansari; Jon Barry; Ioanna Katsiadaki; Melinda Long; Sara Losada; Christopher Martin; Lara Pearson; Marta Vannoni; Alex R.O. Cousins (Marine Pollution Bulletin, 2026)

Global fits and the search for new physics: past, present and future - Peter Athron; Csaba Balázs; Jon Butterworth; Christopher Chang; Andrew Fowlie; Tomás Gonzalo; Adil Jueid; Anders Kvellestad; Michele Lucente; Farvah Mahmoudi; Gregory D. Martinez; Are Raklev; et al. (Science Bulletin, 2026)

Oceanographic and climatic controls of meteoric 10Be fluxes to seafloor sediments: A global synthesis - Jennifer Middleton; Frank Pavia; Robert Anderson; Roseanne Schwartz; Martin Fleisher; Yong Lao; Yuxin Zhou; Christopher Kinsley; Joerg Schaefer; Martin Frank; Gisela Winckler (Quaternary Science Reviews, 2026)

Evaluation of the retention process of bile acids by cell surface of inactivated Lacticaseibacillus rhamnosus GG using spray drying under in vitro digestion simulation - Douglas Xavier-Santos; Rodrigo Dias Requião; Paulo César Martins Alves; Christopher Schmidt; Thomas Kurth; Adriane Elisabete Costa Antunes; Stephanie Bader-Mittermaier; Peter Eisner; Anderson S. Sant’Ana (Food Bioscience, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Advancing Ecological Understanding and Sustainable Management of Small Pelagic Fish - Myron A. Peck; Ignacio A. Catalán; Ryan R. Rykaczewski; Akinori Takasuka; Susana Garrido; Rebecca G. Asch; Matthew R. Baker; Noelle M. Bowlin; Jennifer Boldt; Richard D. Brodeur; Cecilie Hansen; Salvador E. Lluch‐Cota; et al. (Fish and Fisheries, 2026)
Small pelagic fish (SPF) are critical to the trophodynamic structure and function of marine systems and support some of the most valuable and socially important fisheries worldwide. Their “boom and bust” population dynamics, shifts in distribution, and importance as forage resources for other fish stocks place unique challenges to assessing and managing SPF. In response to these challenges, an international working group was formed in 2019 to foster collaboration aimed at closing key knowledge gaps in the ecology and sustainable management of SPF. Here, that group reviews progress made over the last ~10 years and identifies priorities for the next stage of coordinated international collaboration. Key research needs include: (i) enhancing monitoring programs to capture shifts in SPF distribution and incorporating new technologies, from molecular tools and digital imaging to biophysical and ecological modelling, (ii) improving data sharing to better understand life‐history bottlenecks and cross‐regional population dynamics, (iii) advancing process‐based studies on oceanic and trophodynamic interactions to clarify the ecological roles of SPF as both predators and prey, and (iv) conducting bioeconomic and risk analyses to assess the vulnerability of fishing‐dependent human communities to environmental and fish population fluctuations. A key pathway forward involves integrating mechanistic ecological knowledge, ecosystem and bioeconomic modelling, and social‐ecological frameworks into real‐time, adaptive, and equitable management approaches. This integration will be essential for developing resilient, ecosystem‐based fisheries management capable of anticipating tipping points, accommodating non‐stationary population dynamics, and ensuring sustainability under future climate and socio‐economic uncertainties.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

No differences in inhibitory control or prefrontal activation during a cannabis cue stop-signal task across CUDIT-R-defined CUD-risk groups - Christopher R. Pickering; Valentina Lorenzetti; Andrew Jones; Martin Guest; Paul Christiansen; Carl A. Roberts (Psychopharmacology, 2026)
Rationale Cannabis use continues to increase globally, with a growing proportion of users exhibiting problematic patterns of use. Although neural differences in reward and inhibitory control systems are commonly reported in individuals who use cannabis relative to individuals not reporting cannabis use, findings using behavioural tasks are inconsistent. This is possibly due to lack of differentiation between regular and more problematic patterns of use. Objectives This study investigated whether inhibitory control performance and associated prefrontal and orbitofrontal activation differed across CUDIT-R-stratified levels of CUD risk. Methods Participants ( N = 81) were divided into three groups based on CUDIT-R scores: 30 high-CUD-risk individuals who use cannabis (≥ 12), 21 low-CUD-risk individuals who use cannabis (< 8), and 30 individuals not reporting cannabis use. Individuals with a current substance use disorder, including cannabis use disorder, were excluded from participation. All completed a cannabis-cue specific Stop-Signal Task (SST) while functional near-infrared spectroscopy (fNIRS) was used to measure oxygenated (oxyHb) and deoxygenated haemoglobin (deoxyHb) concentrations in the prefrontal cortices. Behavioural performance and neural activation were compared across groups. Results No significant behavioural or neural differences were found between the groups. Conclusions The study found no evidence of impaired inhibitory control or differential prefrontal activation across CUDIT-R-stratified levels of CUD risk. The results suggest incorporating further diagnostic stratification, multimodal imaging, and ecologically valid methods in future research to better characterise cannabis-related neural adaptations and inform clinical practice.

Laboratory safety evaluations of izenivetmab, a caninized anti-nerve growth factor monoclonal antibody, for three-month alleviation of osteoarthritic pain in dogs - Adam Werts; Kayla Saad; Bernard Hummel; Lisa Mangus; Eric Green; Martin Guillot; Cathy Carlson; Agathe Bedard; Rogely Boyce; Christopher S. Knauer; Sarah Roode; Phaedra Cole (The Veterinary Journal, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

How Viscoelastic Effects Impact Polymer Fluid Flow in Porous Media - Yongxin Wang; Si Suo; Callum Cuttle; Christopher W. MacMinn; Martin J. Blunt; Catherine O’Sullivan (Transport in Porous Media, 2026)
Polymer fluids are widely used in subsurface and geotechnical engineering applications. While the steady shear rheology of polymer fluids is known to be reasonably captured by a Carreau-like shear-thinning model, it is still not fully understood how their elastic rheological characteristics, beyond shear-thinning behavior alone, influence their flow in porous media. In this study, we numerically investigate these effects using direct, pore-scale numerical simulations. By comparing data from simulations using the FENE-P model, which incorporates viscoelastic effects, with data from corresponding simulations using the Carreau model, which captures only shear thinning, we confirm that fluid elasticity can induce recirculation upstream of restrictions, leading to a reduction in polymer fluid conductance in porous media. As this recirculation is controlled by the geometric conditions, we conducted detailed comparisons between a two-dimensional model, a three-dimensional model mimicking microfluidics experiments, and an axisymmetric model, analogous to a constricted capillary tube. We also simulate flow in an ordered packing of uniform spheres to develop an understanding of the implications for flow in a 3D porous material. We find that these flows are regulated by the interplay between shear-thinning and elasticity effects. When the shear-thinning effect is sufficiently strong, the effects of elasticity are suppressed. In subsurface applications, viscoelastic effects are significant due to pore-scale confinement and fluid rheology itself, requiring explicit consideration in modeling, pilot design, and performance forecasting. Article Highlights In porous media, the pore geometries control the flow patterns of polymer fluids that have both shear-thinning and elastic characteristics. Upstream recirculation in a single-constriction channel induced by elastic forces takes place in wider pore spaces and develops with increasing Weissenberg number. For flow through a quasi-3D single constriction and a regular lattice packing, a greater energy loss is observed in the case of viscoelastic fluids in comparison with that in the corresponding Carreau fluid. The ratio of the zero-shear-rate viscosity to the infinite-shear-rate viscosity changes the polymer fluid conductance and flow patterns in a single-constriction channel. The extent of the upstream recirculation is proportional to the excessive pressure gradient in the viscoelastic fluid over the corresponding equivalent Carreau fluid.

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Assessing social–ecological feedbacks in small-scale fisheries - Leandro Castello; Adriana Guimarães Abreu; George Christopher Brooks; João Vitor Campos-Silva; Priscila dos Reis Cunha; Ayan Santos Fleischmann; Caetano Lucas Borges Franco; Ana Claudia Gonçalves; Emma Ann Hultin; Holly Kathleen Kindsvater; Eduardo Guimarães Martins; Cristina Isis Buck Silva; et al. (Ambio, 2026)
Assessment frameworks do not capture the complexity of the social–ecological dynamics of small-scale fisheries (SSF), which support millions of livelihoods yet face persistent sustainability challenges. Reciprocal feedbacks between fish populations and fishers that are central to sustainability remain insufficiently integrated into assessment approaches because conventional fisheries management emphasizes population dynamics, whereas social–ecological systems research focuses on social drivers and faces operational challenges. We propose an integrative diagnostic approach that explicitly links fish population dynamics with theories of fisher behavior and governance. We illustrate its application using co-managed arapaima fisheries in the Amazon Basin, where sustainability emerges from multi-scalar social and ecological interactions. By capturing these feedbacks, the approach bridges ecological and social dimensions to identify key drivers of sustainability. It provides a replicable, interdisciplinary framework for diagnosing SSF sustainability and identifying leverage points to support adaptive governance across diverse contexts.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Extensive titanium isotope fractionation in magmatic and hydrothermal mineral systems - Christopher Emproto; Ryan Mathur; Adam C. Simon; Linda Godfrey; Jeffrey D. Vervoort; Mingguang Sun; Courteney Dhnaram; Vladimir Lisitsin; Martin Reich; Fernando Barra (Chemical Geology, 2026)

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Is the seagrass greener on the other side? Faster growth in Biscayne Bay, Florida’s nurse sharks (Ginglymostoma cirratum) compared to neighboring conspecifics of Bimini, The Bahamas - John F. Hlavin; Emily A. Yeager; Christine E. Martin; Christopher J. Will; Nicholas Perni; Christian Pankow; Catherine C. Macdonald (Environmental Biology of Fishes, 2026)
Effective management of vulnerable species requires a precise understanding of life history. In 2024, Fadool et al. published the first von Bertalanffy growth model for the nurse shark ( Ginglymostoma cirratum ), reporting an asymptotic maximum length L ∞ of 303.28 cm and a growth coefficient k of 0.04 yr −1 for the population in Bimini, The Bahamas. We investigated whether nurse shark growth varies in nearby Biscayne Bay, Florida, an adjacent site within the western Atlantic region. We used 37 recaptured nurse sharks from Biscayne Bay to generate a comparable growth model, which estimated a significantly smaller L ∞ of 259.26 cm and a larger k of 0.11 yr −1 than Bimini. Biscayne Bay’s empirical growth rates were significantly higher on average than Bimini and exhibited a significantly steep decrease with increasing shark size not observed in Bimini. Additionally, the minimum linear displacement of 48 recaptured sharks was positively correlated with shark size, suggesting potential site fidelity to a small home range (1.6 ± 2.2 km) that increases with age. Our results indicate that differences in growth can occur over relatively small spatial scales despite environmental and geographic similarities, potentially reflecting genetic differences driven by historic fishing pressure or differences in resource availability. Significant growth rate variation between adjacent shark subpopulations assumed to be ecologically indistinct highlights the importance of sampling across a region’s subpopulations to inform management with more accurate life history data.

Long-term efficiency of cropland management strategies for the mitigation of soil organic carbon losses - David I. Schubert; Christopher Just; Lorenz Heigl; Konrad Offenberger; Michael Diepolder; Ingrid Kögel-Knabner; Martin Wiesmeier (Agriculture, Ecosystems & Environment, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Pathogens in the garden dormouse Eliomys quercinus - Sarah P. Stubbe; Eva Marie Kramer; Sven Büchner; Christine Jelinek; Calvin Mehl; René Ryll; Elisa Heuser; Dania Richter; Donata Hoffmann; Emilija Vasiliūnaitė; Christopher B. Buck; Indrė Kučinskaitė-Kodzė; et al. (European Journal of Wildlife Research, 2026)
Wild rodents are important reservoirs and vectors of various pathogens, and play a crucial role in the spread of zoonotic pathogens. The garden dormouse ( Eliomys quercinus ), an arboreal nocturnal rodent species native to Europe, has declined throughout much of its natural range in recent decades. The reason for this ongoing decline is not yet fully understood, but infectious diseases may play a role. This study aimed to review the diversity of pathogens associated with the garden dormouse. For this purpose, a comprehensive review of the existing literature on garden dormouse-associated viruses, bacteria and protozoa was conducted. In parallel, we analysed samples from 294 garden dormice, that were found dead in Germany, for rodent-associated and zoonotic pathogens. The scientific literature currently, comprising 53 references, covers 73 years and primarily addresses Borrelia spp. and Eimeria myoxi . In the literature, a total of eight pathogens have been detected in garden dormice. In our own investigations, we were able to detect four different pathogens as well as antibodies against hepatitis E virus. The most prevalent pathogen found in our study was Staphylococcus aureus (29%, n = 58). Borrelia spielmanii and B. afzelii were found in 5.6% of garden dormice ( n = 143) and 22% of the ticks attached to garden dormice ( n = 32). This study reports the first documentation of Leptospira spp. in garden dormice, with L . borgpetersenii , serogroup Sejroe, sequence type 197 detected in 2 of 176 animals. Beside these zoonotic pathogens metagenomic sequencing of selected samples revealed representatives of multiple DNA-virus families, including Parvoviridae and Polyomaviridae , most likely without zoonotic potential. There is currently no evidence, either from the literature or from our own investigations, that pathogens play a significant role in the decline of the garden dormouse in Germany.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Zika Virus Reprograms Microglial Mitochondrial Metabolism to Support Immune Activation and Viral Replication: Omega-3 DHA Counteracts Neuroinflammation and Viral Persistence - Heloísa Antoniella Braz-de-Melo; Fernanda Gomes Lago; Rafael Corrêa; Igor de Oliveira Santos; Paula Maria Quaglio Bellozi; Raquel das Neves Almeida; Wagner Fontes; Mariana S. Castro; Aline Maria Araújo Martins; Raphaela Menezes de Oliveira; Nadia Martins Serpa Rossi; Gabriel Pasquarelli-do-Nascimento; et al. (Molecular Neurobiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

CottonSim: A vision-guided autonomous robotic system for cotton harvesting in Gazebo simulation - Thevathayarajh Thayananthan; Xin Zhang; Yanbo Huang; Jingdao Chen; Nuwan K. Wijewardane; Vitor S. Martins; Gary D. Chesser; Christopher T. Goodin (Computers and Electronics in Agriculture, 2025)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Is urine concentration by reverse osmosis economically viable for its reuse as fertiliser? - Chee Xiang Chen; Veera Koskue; Md Sayed Iftekhar; Christopher DF Honig; Gregory J.O. Martin; George Q. Chen; Stefano Freguia (Journal of Environmental Chemical Engineering, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Rift foundering and the generation of non-orogenic granulites during the Mesoproterozoic - Jie Yu; Ben S. Knight; Chris Clark; Christopher L. Kirkland; Martin Hand (Earth and Planetary Science Letters, 2025)

Taken with a grain of salt: Resolving evaporite stratigraphy through accessory mineral geochronology - Jiankang Yi; Christopher L. Kirkland; Julien Bourdet; Milo Barham; Martin Danišík; Andrew Feitz; Peter W. Haines; Brad McDonald; Bruno V. Ribeiro; Emanuelle Frery; Claudio Delle Piane (Earth and Planetary Science Letters, 2025)

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

An expert elicitation to inform coastal management decision-making for mitigating future hazards - Davina L. Passeri; Matthew Richardson; Julien Martin; Simeon Yurek; Karim Alizad; Matthew V. Bilskie; James Flocks; Donya Frank-Gilchrist; Robert L. Jenkins; Rangley C. Mickey; Margaret L. Palmsten; Christopher G. Smith; et al. (Journal of Environmental Management, 2025)

The appropriate environmental sample to educate novice students in environmental radioactivity measurements using gamma ray spectroscopy - Christopher Martin; Kayla Cockerline; Sheldon Landsberger (Journal of Environmental Radioactivity, 2025)

Prenatal exposure to metals and metal mixtures influences birth weight in affected populations in the Republic of Suriname, South America - Jeffrey K. Wickliffe; Ihsan E. Buker; Cassandra Newsom; Hannah H. Covert; Wilco Zijlmans; Firoz Abdoel Wahid; Maureen Y. Lichtveld; Ashna D. Hindori-Mohangoo; Anisma Gokoel; Gaitree Baldewsingh; Martin Shafer; Christa Zaborske; et al. (Environmental Research, 2025)

Species nativeness as a cultural paradigm in conservation - Lily M. van Eeden; Jeff Vance Martin; Jonathan Fisk; Lisa Lehnen; Erle C. Ellis; Michael C. Gavin; Adam C. Landon; Lincoln R. Larson; Kirsten M. Leong; Wayne Linklater; Christopher K. Williams; Richard E.W. Berl (Biological Conservation, 2025)

Rapid Global Deforestation Leaves Forest‐Dependent Raptors With Half of Their Suitable Habitat Remaining - Christopher J. O'Bryan; Zunyi Xie; Hongli Li; Evan R. Buechley; Martin K.‐F. Bader; James R. Allan; Ralph Buij (Global Change Biology, 2025)
Raptors—a group that includes hawks, eagles, owls, and vultures—are among the most imperiled vertebrates, with over half of species declining and one‐fifth threatened with extinction. Most raptors depend on forests for survival, yet the extent and consequences of recent deforestation within their ranges remain poorly understood. We analyzed high‐resolution global data on forest change between 2001 and 2023 within the ranges of 369 forest‐dependent raptor species. On average, these species have lost 10% of forest within their ranges since 2001. Seventy‐seven species had already lost at least 15% of additional forest cover within their ranges in the latter half of the 20th century. Currently, only 52% of forest cover remains within forest‐dependent species' ranges on average, with many forest specialists retaining less than 25% cover. Forest‐dependent raptors listed as Critically Endangered by the IUCN have lost the most forest and now retain the least forest cover within their ranges. Shifting agriculture is the primary driver of forest loss—particularly in tropical Africa and South America—followed by commodity‐driven deforestation in Southeast Asia. Because forest loss is frequently used as a proxy for extinction risk for raptors, our findings have direct applications for species threat assessments, regional conservation priorities, and global biodiversity commitments.

‘What have I just eaten?’ A qualitative exploration of awareness and use of ultra-processed food products during pregnancy and the post-partum period in line with the COM-B behaviour model - Fiona Lavelle; Catherine V. George; Claire McKernan; Carla A. Martins; Vanessa A. Shrewsbury; Julia A. Wolfson; Rachael M. Taylor; Kerith Duncanson; Christopher Elliott; Clare E. Collins (Appetite, 2025)

Potential molecular mechanisms of Silexan® identified by RNA- Sequencing in a mouse model of chronic social stress-induced excessive aversion sensitivity - Sabrina Weisenburger; Thomas Gantert; Hannes Sigrist; Christopher R. Pryce; Martin D. Lehner (Phytochemistry Letters, 2025)

Natural and artificial radionuclides in rocks and soils of the Galápagos Islands - Severina Zita Irsigler; Martin Hubert Gerzabek; Christopher Lüthgens; Franz Zehetner (Journal of South American Earth Sciences, 2025)

The potential impact of forest loss on drinking water treatment costs in the southeastern U.S. - Arpita Nehra; Justin S. Baker; Peter V. Caldwell; Katherine L. Martin; Travis W. Warziniack; Richard H. Manner; Christopher M. Mihiar; Gregory E. Frey; Jennifer K. Costanza (Forest Policy and Economics, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Improving presurgical language mapping by a method for optimally sorting independent components of resting-state fMRI - Beatriz Vale; Diogo Duarte; Ricardo Vigário; Christopher Benjamin; Pedro Vilela; Martin Lauterbach; Alexandre Andrade (Brain Imaging and Behavior, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Peak oxygen uptake in older adults with heart failure: a systematic review and meta-analysis - Veronika Schmid; Sarah Paterson; Christopher Weinkauf; Jing Wang; Corey R. Tomczak; David Niederseer; Jan Vontobel; Daniel E. Forman; Martin Halle; Michael D. Nelson; Stephen J. Foulkes; Mark J. Haykowsky (GeroScience, 2025)

Controlled hyperthermia by flying-foxes in the wild: understanding mammalian tolerance to hotter summer conditions - Melissa J. Walker; Justin A. Welbergen; Jessica Meade; Wayne S.J. Boardman; Terry Reardon; John M. Martin; Adam McKeown; Christopher Turbill (Journal of Thermal Biology, 2025)

Magnesian-suite volcanism and ancient crust building on the Moon 4.25 billion years ago - Christopher Yen; Cécile Deligny; Bradley Jolliff; Alexander Nemchin; Paul Carpenter; Martin Whitehouse; Renaud Merle; Ryan Ogliore; Jeremy Kent; Ryan Zeigler; Juliane Gross; Scott Eckley; et al. (Earth and Planetary Science Letters, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Trophic ecologies and dietary niches of Arctic charr (Salvelinus alpinus) and three coastal forage fishes in Frobisher Bay, Nunavut - Sarah Rauf; Ashley Ehrman; Christopher Lewis; Zoya Martin; Ross Tallman; Andrea Niemi (Environmental Biology of Fishes, 2025)
Here, the trophic ecology of four mid-trophic level fishes is described for an Arctic coastal marine habitat near Iqaluit, Nunavut. Arctic charr ( Salvelinus alpinus ), Arctic cod ( Boreogadus saida ), Fish Doctor ( Gymnelus viridis ), and sculpins (Cottidae) diet and feeding strategies were estimated using gut content; dietary niches were compared using stable isotopes (δ 13 C, δ 15 N); and relationships between diet indices and metrics of fish condition, including calorie content, were assessed. While the four taxa differed in foraging strategy, targeted prey, and the strength of associations with benthic and pelagic food web pathways, niche overlap occurred among the benthic and pelagic taxa. Pelagic Arctic charr and Arctic cod specialized in hyperbenthic amphipods and copepods, respectively, with evidence that selectivity was flexible. Fish Doctor and sculpins were benthic generalists with evidence for inter-individual and population-level specialization. Arctic charr occupied a central isotopic niche, resulting in a high probability of dietary niche overlap with the other three taxa. Fish Doctor and sculpins were likely to overlap with each other, and both had a low probability of overlap with Arctic cod. Isotopic diet indicators did not significantly explain variation in fish condition or calorie content. Findings reiterate the complex trophic ecologies that allow Arctic fish to divide resources and respond to changes in prey availability.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Confronting the interconnection of chemical pollution and climate change - Simona A. Bălan; Saskia K. van Bergen; Ann Blake; Topher Buck; Scott Coffin; Jamie C. DeWitt; Gretta Goldenman; Frank A. von Hippel; Sophia von Hippel; Christopher P. Leonetti; David Rist; Martin Scheringer; et al. (Environmental Innovation and Societal Transitions, 2025)

Spatial variation in population abundance of invasive Rattus rattus across coastal habitats of East African island archipelago - Teclamageni S. Mayeji; Nsajigwa E. Mbije; Christopher A. Sabuni; David J. Kavana; Amina R. Issae; Martin J. Martin (Acta Oecologica, 2025)

Bird migration on the edge: Experimental manipulation of corticosterone advances departure dates - Maëliss Hoarau; Frédéric Dulude‐de Broin; Frédéric LeTourneux; Frédéric Angelier; Maude Gauthier‐Bouchard; Marie‐Claude Martin; Akiko Kato; Josée Lefebvre; Philippe J. Thomas; Christopher K. Williams; Joël Bêty; Pierre Legagneux (Ecology, 2025)
Endogenous reserves accumulated during migration stopovers help most migratory birds cope with environmental uncertainties and fuel energy demands associated with migration and/or reproduction. Migratory decisions, such as departure time, should thus be finely tuned to energy intake rate at stopover sites. However, the physiological drivers of these decisions remain poorly understood. Glucocorticoids such as corticosterone (CORT) are known to mediate the stress response in birds but also play a key role in the regulation of energy intake and behavior, particularly during demanding life‐history stages. We investigated how baseline CORT influences bird energy acquisition and migratory decisions by manipulating the physiology of wild snow geese ( Anser caerulescens atlanticus ) through subcutaneous implantation of corticosterone pellets during spring stopover. Birds of similar body condition were paired, implanted with CORT or placebo pellets, and tracked with GPS–GSM collars and accelerometers to monitor foraging efforts, habitat use, and migration departure date. We measured foraging rates from accelerometer data and classified using an unsupervised algorithm calibrated with field video recordings. CORT‐treated birds foraged 20% more on average than placebo individuals over 10 days, primarily by increasing foraging efforts rather than altering habitat use. Most of the difference occurred in the first days post‐implantation (Foraging rates on Day 2, CORT: 0.4 [95% CI: 0.34, 0.47]; placebo: 0.3 [0.2, 0.36]) and gradually faded to zero afterward (Foraging rates on Day 10, CORT: 0.26 [0.21, 0.32]; placebo: 0.26 [0.21, 0.31]). These higher foraging rates advanced the median departure date of CORT‐treated individuals by 2 days compared to placebo (median departure: CORT, May 17 [15, 17]; placebo, May 19 [17, 20]). Our experimental manipulation is one of the first to induce a positive shift in migration phenology and confirms the role of CORT baseline levels in modulating energy acquisition and migratory decisions in a wild bird species.

Development of a Detailed Finite Element Model of the BIPED MK2 and Verification of Fidelity in Two Cases of Blunt Impact - Robert Chauvet; Ashton Martin; Jennifer Rovt; Oren Petel; Simon Ouellet; Lindsey Westover; Christopher R. Dennison (Annals of Biomedical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Pan-Canadian Predictive Modeling of Lithium–Cesium–Tantalum Pegmatites with Deep Learning and Natural Language Processing - Mohammad Parsa; Christopher J. M. Lawley; Tarryn Cawood; Tania Martins; Renato Cumani; Steven E. Zhang; Aaron Thompson; Ernst Schetselaar; Steve Beyer; David R. Lentz; Jeff Harris; Hossein Jodeiri Akbari Fam; et al. (Natural Resources Research, 2025)
The discovery of new lithium resources is essential because lithium plays a vital role in the manufacturing of green technology. Along with brines and volcano–sedimentary deposits, approximately a one-third share of global lithium resources is associated with lithium-cesium-tantalum (LCT) pegmatites, with Canada hosting numerous examples. This research applied generative adversarial networks, natural language processing, and convolutional neural networks to generate mineral prospectivity models and support exploration targeting for Canadian LCT pegmatites. Geoscientific text data included within public bedrock geology maps and natural language processing were used to convert conceptual targeting criteria into evidence layers that complement more traditional, geophysical and geochronological data used for mineral prospectivity modeling (MPM). A multilayer architecture of convolutional neural networks, including an attention mechanism, was designed for data modeling. This architecture was trained and validated using variable synthetically generated class labels, input image sizes, and hyperparameters, resulting in an ensemble of 1000 models. The uncertainty of the ensemble was analyzed using a risk–return analysis, yielding a bivariate choropleth risk–return plot that facilitates the interpretation of prospectivity models for downstream applications. This was further complemented by employing post hoc interpretability algorithms to translate the black-box nature of neural networks into comprehensible content. The low-risk and high return class of our prospectivity models reduces the search space for discovering LCT pegmatites by 88%, delineating 99% of known LCT pegmatites in Canada. The results of this study suggest that our workflow (i.e., combining synthetic data generation, natural language processing, convolutional neural networks, and uncertainty propagation for MPM) facilitates decision-making for regional-scale lithium exploration and could also be applied to other mineral systems.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Integrating the Bright and Dark Sides of Aquatic Resource Subsidies—A Synthesis - Cornelia W. Twining; Andreu Blanco; Christopher Dutton; Martin J. Kainz; Eric Harvey; Carmen Kowarik; Johanna M. Kraus; Dominik Martin‐Creuzburg; Tarn Preet Parmar; N. Roxanna Razavi; Nicole Richoux; Gregoire Saboret; et al. (Ecology Letters, 2025)
Aquatic and terrestrial ecosystems are linked through the reciprocal exchange of materials and organisms. Aquatic‐to‐terrestrial subsidies are relatively small in most terrestrial ecosystems, but they can provide high contents of limiting resources that increase consumer fitness and ecosystem production. However, they also may carry significant contaminant loads, particularly in anthropogenically impacted watersheds. Global change processes, including land use change, climate change and biodiversity declines, are altering the quantity and quality of aquatic subsidies, potentially shifting the balance of costs and benefits of aquatic subsidies for terrestrial consumers. Many global change processes interact and impact both the bright and dark sides of aquatic subsidies simultaneously, highlighting the need for future integrative research that bridges ecosystem as well as disciplinary boundaries. We identify key research priorities, including increased quantification of the spatiotemporal variability in aquatic subsidies across a range of ecosystems, greater understanding of the landscape‐scale extent of aquatic subsidy impacts and deeper exploration of the relative costs and benefits of aquatic subsidies for consumers.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Soil carbon benchmarks and cropland management effects: Insights from the Bavarian soil organic matter monitoring - Manuel Sümmerer; Christopher Just; Martin Wiesmeier (Geoderma Regional, 2025)

Trace element and isotope composition of calcite, apatite, and zircon associated with magmatic sulfide globules - Maria Cherdantseva; Marco L. Fiorentini; Christopher M. Fisher; Antony I. S. Kemp; Laure A. J. Martin; Matvei Aleshin; Malcolm P. Roberts (Mineralium Deposita, 2025)
The formation of volatile-rich phases in magmatic sulfide systems has been interpreted at least in six different ways. The most popular model attributes their origin to secondary processes, mostly due to the presence of serpentine, chlorite, phlogopite, amphibole, and calcite. While chlorite and serpentine are likely to form as alteration products, the other volatile-rich minerals have the potential to originate in a range of ways, including by primary magmatic processes. Based on mineralogical and petrological studies, it was recently suggested that volatile- and incompatible element-rich halos around sulfide globules may form due to the interaction between three immiscible liquids: silicate, carbonate, and sulfide. This hypothesis was confirmed by experimental data revealing the systematic envelopment of sulfide globules by carbonate melt, indicating their mutual affinity. In this study, we present data on isotopic signatures and trace element distributions of three minerals commonly found in spatial association with sulfides—calcite, apatite, and zircon—to address the question of the source and nature of volatiles and other incompatible elements involved in the formation of the halos. Here we compare our new hypothesis with all the previously proposed explanations to show if they can be consistent with obtained results. Our findings indicate that both mantle and crustal sources play a role in the formation of volatile- and incompatible element-rich halos, strongly correlating with sulfur isotope data previously reported for the sulfide globules in the same intrusions. This correlation confirms the shared origin of sulfides, carbonate and fluids during ore-forming processes, ruling out the secondary origin of volatile-rich phases. The isotope and trace element signatures support the newly proposed hypothesis that volatile- and incompatible element-rich halos could have been formed due to the interaction of immiscible sulfide, carbonate, and silicate melts. The volatile-rich carbonate melt could be sourced from the mantle or it could be added from the crust. Regardless of the origin, carbonate melt and sulfide liquid both immiscible with mafic magma tend to stick to each other resulting in the formation of volatile- and incompatible element-rich halos commonly documented in magmatic sulfide deposits.

Deep-sea drilling of the 13°30′ N oceanic core complex: Assessing links between fluid flow, metal enrichment and seafloor massive sulfide deposit formation near Semenov-1 - Andrew J. Martin; Bramley J. Murton; Christopher J. MacLeod; John W. Jamieson; Isobel I. Yeo; Sven Petersen; Katie A. McFall; Simon Allerton; Anna Lichtschlag; Christian Bishop; Acer Figueroa; Szu-Ying Lai (Lithos, 2025)

Habitat heterogeneity over multiple scales supports dense and diverse megafaunal communities on a northeast Pacific ridge - Fanny Girard; David W. Caress; Jennifer B. Paduan; Linda A. Kuhnz; Steven Y. Litvin; Emma Flattery; Amanda S. Kahn; Andrew DeVogelaere; Erica J. Burton; Christopher Lovera; Eric J. Martin; James P. Barry (Limnology and Oceanography, 2025)
Marine environments are highly heterogeneous, varying across scales of a few meters to entire ocean basins. Understanding the relationship between environmental variability and species distribution is essential for area‐based management and conservation. However, this requires a precise alignment of seabed mapping with environmental and biological sampling, which is often difficult to achieve in the deep sea. There is thus an urgent need to tackle this challenge to effectively manage high‐diversity habitats such as deep‐sea coral and sponge aggregations. Relying on multiple subsea platforms, seafloor mapping, and imaging techniques, we mapped the distribution of megafaunal communities at Sur Ridge (780–1525‐m depth; off central California) across multiple spatial scales. First, remotely operated vehicle video transects were conducted to characterize community distribution along the ridge in relation to substratum type, environmental conditions, and 1‐m resolution bathymetry. Five distinct communities, located in specific areas of the ridge, were identified. These communities were primarily structured by depth, availability of hard substrata, and terrain complexity (slope and rugosity). Indicator taxa were identified for each community and their distributions were characterized at the centimeter scale from coregistered 5‐mm resolution photomosaic and 5‐cm lateral resolution bathymetry produced during low altitude remotely operated vehicle surveys. High‐resolution mapping allowed the identification of associations between deep‐sea coral and sponge and other benthic taxa and showed that, even at these small scales, different taxa associate with distinct microhabitats. These results highlight the importance of accounting for habitat heterogeneity, and its role in supporting biodiversity when designing management and conservation strategies.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Enhanced bed shear stress and mixing in the tidal wake of an offshore wind turbine monopile - Martin J. Austin; Christopher A. Unsworth; Katrien J. J. Van Landeghem; Ben J. Lincoln (Ocean Science, 2025)
Tidal flow past offshore wind farm (OWF) infrastructure generates a turbulent vortex wake. The wake is hypothesised to enhance seabed stress and water column turbulence mixing, thereby affecting seabed mobility, water column stratification and the transport of nutrients and oxygen and resulting in ecological impacts. We collect novel hydrodynamic data 40 m from an OWF monopile over a spring–neap cycle and use high-frequency velocity measurements to quantify turbulence. Outside of the wake, we observe a classical depth-limited boundary layer, with strong turbulence production and dissipation forced by tidal shear at the seabed. Inside the wake, turbulence production, dissipation and stress are enhanced throughout the full water column and are maximised in the upper half of the water column, where they correspond to a strong mean velocity deficit. Our results show that the seabed drag coefficient is doubled from Cd=3.5×10-3 to 7.8×10-3, suggesting greater seabed mobility, and the eddy viscosity is increased by 1 order of magnitude, indicating enhanced water column mixing. This research provides some valuable insight as OWFs expand into deeper seasonally stratified waters using both bottom-fixed and floating structures, where the addition of enhanced wake turbulence may have broad impacts as the additional mixing energy is added to regions with low rates of background mixing.

Corrigendum to “Limited cougar recolonization of eastern North America predicted by an individual-based model” [Biol. Conserv. volume 298 (2024)/110756] - Thomas W. Glass; Richard A. Beausoleil; L. Mark Elbroch; Brian N. Kertson; Benjamin T. Maletzke; Quinton Martins; Marc R. Matchett; T. Winston Vickers; Christopher C. Wilmers; Heiko U. Wittmer; Hugh Robinson (Biological Conservation, 2025)

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

A deep dive into the waterbird community of an urban oasis: implications for park management - August Wise; Anya Rosener; Arina Martin; Melissa Cote; Christopher D. Hopwood; Elizabeth Schwartz; Riley Tharp; Stephen Blake (Urban Ecosystems, 2024)

Predicting Water Content and Saturation in Mine Tailings with an Electromagnetic Soil Moisture Sensor - Garret M. Martin; Christopher A. Bareither (Mine Water and the Environment, 2024)

Winners and Losers From Climate Change: An Analysis of Climate Thresholds for Tree Growth and Survival for Roughly 150 Species Across the Contiguous United States - Christopher M. Clark; Justin G. Coughlin; Jennifer Phelan; Gray Martin; Kemen Austin; Marwa Salem; Robert D. Sabo; Kevin Horn; R. Quinn Thomas; Rebecca M. Dalton (Global Change Biology, 2024)
Changes in temperature and precipitation are already influencing US forests and that will continue in the future even as we mitigate climate change. Using spatiotemporally matched data for mean annual temperature (MAT) and mean annual precipitation (MAP), we used simulated annealing to estimate critical thresholds for changes in the growth and survival of roughly 150 tree species (153 spp. for growth, 159 spp. for survival) across the conterminous United States (CONUS). We found that growth of nearly one‐third of tree species assessed (44 spp.) decreased with any increase in MAT (42–49 species), whereas fewer responded negatively to projected regional trends in MAP (

Whole-life greenhouse gas emission reduction and removal strategies for buildings: Impacts and diffusion potentials across EU Member States - Nicolas Alaux; Christopher Marton; Jacob Steinmann; Dominik Maierhofer; Alessio Mastrucci; Danai Petrou; Tajda Potrč Obrecht; Delphine Ramon; Xavier Le Den; Karen Allacker; Alexander Passer; Martin Röck (Journal of Environmental Management, 2024)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Late Cenozoic alkali basalts and their interactions with the paleo-Hron River (Western Carpathians): New insights from geochronology and fluvial morphometric indices - Roberta Prokešová; Martin Danišík; Markus Fiebig; Fred Jourdan; Christopher Lüthgens; Juraj Procházka; Juraj Holec; Jozef Minár (Geomorphology, 2024)

Limited cougar recolonization of eastern North America predicted by an individual-based model - Thomas W. Glass; Richard A. Beausoleil; L. Mark Elbroch; Brian N. Kertson; Benjamin T. Maletzke; Quinton Martins; Marc R. Matchett; T. Winston Vickers; Christopher C. Wilmers; Heiko U. Wittmer; Hugh Robinson (Biological Conservation, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Microstructural control on the trace element distribution and Au concentration in pyrite nodules - Riccardo Graziani; Duane C. Petts; Jean-Luc Pilote; Simon E. Jackson; Daniele Regis; Christopher J.M. Lawley; Matthew Polivchuk; Yannick Bussweiler; Martin Rittner (Geochemistry, 2024)

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Regional foraging areas of green turtles (Chelonia mydas) nesting at Aldabra Atoll: insights from stable isotopes and satellite telemetry - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A’Bear; Maria Bielsa; Christopher W. Jones; Martin C. van Rooyen; Brian Souyana; Frauke Fleischer-Dogley; Simona A. Ceriani (Biodiversity and Conservation, 2024)
Sea turtles spend the majority of their lives at foraging grounds. These areas are important for population persistence but generally occur in coastal habitats, which are under increasing human pressure. Identifying key foraging areas is therefore an important step to understanding critical sea turtle habitats, and therefore their threats. Isotope ratios ( δ 15 N, δ 13 C) from skin tissues of 90 green turtles ( Chelonia mydas ) nesting at the regionally important rookery of Aldabra Atoll, Seychelles, were analyzed with samples collected during two periods: 51 samples from March to September 2021, and 39 samples from January to April 2022. These analyses were complemented by nine satellite tracks to identify key foraging areas. Hierarchical clustering and discriminant function analysis identified two main foraging areas: the East African coast (Tanzania and Somalia) and northern Madagascar. Isotopic values indicated that the majority of green turtles nesting at Aldabra forage at one of these two areas, with slightly more green turtles visiting the East African coast. Geographical isotopic patterns were not found latitudinally, suggesting a potential limit to this approach for coastal areas in the Western Indian Ocean. However, we found longitudinal variation of δ 13 C and δ 15 N that few studies have reported. This is the first study in this region to combine satellite telemetry and stable isotope analysis to assign likely foraging areas of green turtles and advances understanding of the complex migration patterns and foraging ecology of this species. We demonstrate the potential and the limitations of stable isotope analysis for identifying/characterizing green turtle foraging areas in this region.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Shifts in macroalgae composition alters carbon flow in Coastal Baltic Sea ecosystems: implications for dissolved organic carbon bioavailability and flux - Jack R. Hall; Kristjan Herkül; Federico Baltar; Christopher D. Hepburn; Georg Martin (Frontiers in Marine Science, 2024)
The extracellular release of dissolved organic carbon (DOC) from marine macroalgae supports coastal ecosystem function by supplying photosynthetically fixed carbon to higher trophic levels via the microbial loop. Despite its widely acknowledged biogeochemical importance, DOC is not typically included in primary production estimates of coastal systems. Additionally, little is known about how changes in species composition and coverage will affect the supply of DOC to coastal systems. Within the context of the Baltic Sea, anthropogenic forces are driving a decline in habitat forming kelp species ( Fucus vesiculosus ) which is superseded by filamentous/turfing algal species, a pattern of change observed globally in numerous other aquatic systems. To evaluate how the drivers of this change may impact the flow of carbon within the Baltic Sea coastal system, the production of DOC by the filamentous algae ( Ectocarpus siliculosus ) was examined and its rate of release determined (0.095 mg C · g DW −1 · h −1 in light and 0.070 mg C · g DW −1 · h −1 in dark). In addition, bioassays were used to assess the short-term DOC use by bacteria as a proxy of the lability of the released products, with the majority (28.7% released in light and 18.6% released in dark) of the products remaining after 120 hours. This data was linked with long term macroalgae biomass and coverage surveys in order to assess changes in macroalgae community structure through time and to produce standing stock estimates of F. vesiculosus. DOC production as a metric of algal coverage was used to make a preliminary estimation of how changes in community structure may impact the flow of carbon within the system. Our results suggest that decreased levels of DOC released by filamentous algae relative to F. vesiculosus will act to reduce microbial activity. Our model estimates the presence of approximately 150,000 tonnes of F. vesiculosus (dry weight) within the Estonian coastal system translating to an annual release of 7,391 tonnes of DOC. Our study indicates that filamentous-dominated systems have likely altered carbon flow, impacting the broader ecology of the Baltic Sea. Consequently, the loss of kelp species and the expansion of filamentous algae may alter carbon dynamics, with important ecological consequences for other coastal systems globally.

Intrusive mechanism of the 2018 Sierra Negra Galápagos eruption, constrained by 4D tomographic images - Meysam Rezaeifar; Christopher J. Bean; James Grannell; Martin Möllhoff; Andrew F. Bell (Journal of Volcanology and Geothermal Research, 2024)

Evaluating the application of texture and chemistry of detrital tourmaline as an indicator of porphyry Cu mineralization: A case study from the Casino porphyry Cu-Au-Mo deposit, Yukon, Canada - Christopher E. Beckett-Brown; Andrew M. McDonald; M. Beth McClenaghan; Martin W. McCurdy (Journal of Geochemical Exploration, 2024)

Elevated mercury exposure in bird communities inhabiting Artisanal and Small-Scale Gold Mining landscapes of the southeastern Peruvian Amazon - Jessica N. Pisconte; Claudia M. Vega; Christopher J. Sayers; C. Steven Sevillano-Ríos; Martin Pillaca; Edwin Quispe; Vania Tejeda; Cesar Ascorra; Miles R. Silman; Luis E. Fernandez (Ecotoxicology, 2024)

Fine-scale foraging ecology and habitat use of sympatric green and hawksbill turtles in the Western Indian ocean - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A'Bear; Veronique Banane; Frances Benstrong; Maria Bielsa; Christopher W. Jones; Anna Koester; Susan Murasko; Martin C. van Rooyen; Frauke Fleischer-Dogley; et al. (Marine Environmental Research, 2024)

Dislocation-mediated interfacial re-equilibration of pyrite: An alternative model to interface-coupled dissolution-reprecipitation and gold remobilisation - Denis Fougerouse; Steven M. Reddy; Sumail; Joël Brugger; Nicolas Thébaud; William D.A. Rickard; Lin Yang; Zakaria Quadir; Malcolm P. Roberts; Andrew G. Tomkins; Laure Martin; Laura Petrella; et al. (Geochimica et Cosmochimica Acta, 2024)

Ecological forestry treatments affect fine-scale attributes within large experimental units to influence tree growth, vigor, and mortality in ponderosa pine/white fir forests in California, U.S. - Christopher E. Looney; Emily G. Brodie; Christopher J. Fettig; Martin W. Ritchie; Eric E. Knapp (Forest Ecology and Management, 2024)

Geochemical proxies for deep-sea temperature and nutrient content in cold-water bamboo corals - Thomas J. Williams; Christopher D. Standish; Philippe Archambault; Jasmin A. Godbold; Martin Solan; Orestis L. Katsamenis; Philip J. Basford; Gavin L. Foster (Chemical Geology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Periodicities observed in the solar and geomagnetic indexes and in SABER thermospheric infrared power measurements - Nabil Nowak; Martin G. Mlynczak; Linda Hunt; B. Thomas Marshall; Christopher J. Mertens (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Mapping alien and native forest dynamics in Chile using Earth observation time series analysis - Pilar Martin-Gallego; Christopher G. Marston; Adison Altamirano; Aníbal Pauchard; Paul Aplin (Forest Ecology and Management, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The differences in drug disposition gene induction by rifampicin and rifabutin are unlikely due to different effects on important pregnane X receptor (NR1I2) splice variants - Julie Nilles; Johanna Weiss; Martin Masin; Christopher Tuffs; Moritz J. Strowitzki; Walter E. Haefeli; Stephanie Ruez; Dirk Theile (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Rifampicin and rifabutin can activate the pregnane X receptor (PXR, NR1I2 ), thereby inducing pharmacokinetically important genes/proteins and reducing exposure to co-administered drugs. Because induction effects vary considerably between these antibiotics, differences could be due to unequal rifamycin-induced activation or tissue expression of the three major NR1I2 splice variants, PXR.1 (NM_003889), PXR.2 (NM_022002), and PXR.3 (NM_033013). Consequently, PXR activation (PXR reporter gene assays) and mRNA expression levels of total NR1I2 , PXR.1, PXR.2, and PXR.3 were investigated by polymerase chain reaction in colon and liver samples from eleven surgical patients, in LS180 cells, and primary human hepatocytes. Compared to the colon, total NR1I2 mRNA expression was higher in the liver. Both tissues showed similar expression levels of PXR.1 and PXR.3, respectively. PXR.2 was not quantifiable in the colon samples. Rifampicin and rifabutin similarly enhanced PXR.1 and PXR.2 activity when transfected into LS180 cells, while PXR.3 could not be activated. In LS180 cells, rifampicin (10 μM) reduced total NR1I2 and PXR.3 expression 2-fold after 24 h, while rifabutin (10 μM) increased total NR1I2 , PXR.1, PXR.2, and PXR.3 mRNA by approx. 50% after 96-h exposure. In primary human hepatocytes, rifampicin (10 μM) suppressed total NR1I2 , PXR.1, and PXR.3 after 48-h exposure, and rifabutin (10 μM) had no significant impact on total NR1I2 or any of the splice variants studied. In conclusion, both antibiotics activated the studied PXR splice variants similarly but modified their expression differently. While rifampicin can suppress mRNA of PXR forms, rifabutin rather increases their expression levels.

Species-specific responses of macrophyte production to the increasing CO2 environment with potential ecosystem implications involved in the Baltic Sea - Liina Pajusalu; Gerli Albert; Evangeline Fachon; Christopher D. Hepburn; Jonne Kotta; Anneliis Kõivupuu; Tiina Paalme; Daniel W. Pritchard; Arno Põllumäe; Kaire Torn; Georg Martin (Journal of Applied Phycology, 2024)

Successful DNA amplification of DNA from non-destructive buccal swabbing in Vespertilionid and Rhinolophid bats - Morgan Hughes; Scott K Brown; Rémi Martin; Christopher H Young; Simon Maddock (Conservation Genetics Resources, 2024)
Acquiring DNA from wild bats (Mammalia: Chiroptera) is typically undertaken utilizing highly invasive (but non-lethal) sampling techniques comprising wing biopsies and occasional blood samples. While non-invasive sampling is possible through the extraction of DNA from faecal samples, it is not always possible to acquire samples from individual bats whilst conducting fieldwork, and as such, this method is primarily applicable to roost occupancy identification. Similarly, wing swabbing is liable to cross-contamination from roost mates. Here we present the first use of oral (buccal) swabbing for successful, species-resolution DNA sequencing of Vespertilionidae and Rhinolophidae in 10 bat species (nine Vespertilionidae and one Rhinolophidae) from the UK.

Valuing water: A global survey of the values that underpin water decisions - Christopher Schulz; Lukas J. Wolf; Julia Martin-Ortega; Klaus Glenk; Maarten Gischler (Environmental Science & Policy, 2024)

The FluidFlower Validation Benchmark Study for the Storage of CO$$_2$$ - Bernd Flemisch; Jan M. Nordbotten; Martin Fernø; Ruben Juanes; Jakub W. Both; Holger Class; Mojdeh Delshad; Florian Doster; Jonathan Ennis-King; Jacques Franc; Sebastian Geiger; Dennis Gläser; et al. (Transport in Porous Media, 2024)
Successful deployment of geological carbon storage (GCS) requires an extensive use of reservoir simulators for screening, ranking and optimization of storage sites. However, the time scales of GCS are such that no sufficient long-term data is available yet to validate the simulators against. As a consequence, there is currently no solid basis for assessing the quality with which the dynamics of large-scale GCS operations can be forecasted. To meet this knowledge gap, we have conducted a major GCS validation benchmark study. To achieve reasonable time scales, a laboratory-size geological storage formation was constructed (the “FluidFlower”), forming the basis for both the experimental and computational work. A validation experiment consisting of repeated GCS operations was conducted in the FluidFlower, providing what we define as the true physical dynamics for this system. Nine different research groups from around the world provided forecasts, both individually and collaboratively, based on a detailed physical and petrophysical characterization of the FluidFlower sands. The major contribution of this paper is a report and discussion of the results of the validation benchmark study, complemented by a description of the benchmarking process and the participating computational models. The forecasts from the participating groups are compared to each other and to the experimental data by means of various indicative qualitative and quantitative measures. By this, we provide a detailed assessment of the capabilities of reservoir simulators and their users to capture both the injection and post-injection dynamics of the GCS operations.

Movements of anadromous coastal cutthroat trout (Oncorhynchus clarkii clarkii) in Puget Sound, Washington, USA - Thomas P. Quinn; Martin C. Arostegui; Christopher S. Ellings; Frederick Goetz; James P. Losee; Joseph M. Smith; Sarah R. Zaniewski (Environmental Biology of Fishes, 2024)

Diving behavior in semi-aquatic Anolis lizards results in heat loss with sex-specific cooling tolerance - Alexandra M. Martin; Christopher K. Boccia; Lindsey Swierk (Behavioral Ecology and Sociobiology, 2024)

The paradigm change from reactive medical services to 3PM in ischemic stroke: a holistic approach utilising tear fluid multi-omics, mitochondria as a vital biosensor and AI-based multi-professional data interpretation - Olga Golubnitschaja; Jiri Polivka; Pavel Potuznik; Martin Pesta; Ivana Stetkarova; Alena Mazurakova; Lenka Lackova; Peter Kubatka; Martina Kropp; Gabriele Thumann; Carl Erb; Holger Fröhlich; et al. (EPMA Journal, 2024)
Worldwide stroke is the second leading cause of death and the third leading cause of death and disability combined. The estimated global economic burden by stroke is over US$891 billion per year. Within three decades (1990–2019), the incidence increased by 70%, deaths by 43%, prevalence by 102%, and DALYs by 143%. Of over 100 million people affected by stroke, about 76% are ischemic stroke (IS) patients recorded worldwide. Contextually, ischemic stroke moves into particular focus of multi-professional groups including researchers, healthcare industry, economists, and policy-makers. Risk factors of ischemic stroke demonstrate sufficient space for cost-effective prevention interventions in primary (suboptimal health) and secondary (clinically manifested collateral disorders contributing to stroke risks) care. These risks are interrelated. For example, sedentary lifestyle and toxic environment both cause mitochondrial stress, systemic low-grade inflammation and accelerated ageing; inflammageing is a low-grade inflammation associated with accelerated ageing and poor stroke outcomes. Stress overload, decreased mitochondrial bioenergetics and hypomagnesaemia are associated with systemic vasospasm and ischemic lesions in heart and brain of all age groups including teenagers. Imbalanced dietary patterns poor in folate but rich in red and processed meat, refined grains, and sugary beverages are associated with hyperhomocysteinaemia, systemic inflammation, small vessel disease, and increased IS risks. Ongoing 3PM research towards vulnerable groups in the population promoted by the European Association for Predictive, Preventive and Personalised Medicine (EPMA) demonstrates promising results for the holistic patient-friendly non-invasive approach utilising tear fluid-based health risk assessment, mitochondria as a vital biosensor and AI-based multi-professional data interpretation as reported here by the EPMA expert group. Collected data demonstrate that IS-relevant risks and corresponding molecular pathways are interrelated. For examples, there is an evident overlap between molecular patterns involved in IS and diabetic retinopathy as an early indicator of IS risk in diabetic patients. Just to exemplify some of them such as the 5-aminolevulinic acid/pathway, which are also characteristic for an altered mitophagy patterns, insomnia, stress regulation and modulation of microbiota-gut-brain crosstalk. Further, ceramides are considered mediators of oxidative stress and inflammation in cardiometabolic disease, negatively affecting mitochondrial respiratory chain function and fission/fusion activity, altered sleep–wake behaviour, vascular stiffness and remodelling. Xanthine/pathway regulation is involved in mitochondrial homeostasis and stress-driven anxiety-like behaviour as well as molecular mechanisms of arterial stiffness. In order to assess individual health risks, an application of machine learning (AI tool) is essential for an accurate data interpretation performed by the multiparametric analysis. Aspects presented in the paper include the needs of young populations and elderly, personalised risk assessment in primary and secondary care, cost-efficacy, application of innovative technologies and screening programmes, advanced education measures for professionals and general population—all are essential pillars for the paradigm change from reactive medical services to 3PM in the overall IS management promoted by the EPMA.

Crustal growth in the Archean: Insights from zircon petrochronology of the far-east Yilgarn Craton, Western Australia - Ravi Schreefel; Christopher M. Fisher; Anthony I. S. Kemp; Steffen G. Hagemann; Quentin Masurel; Nicolas Thébaud; Clayton Davy's; Laure A. J. Martin; Jack R. Lowrey; Yongjun Lu; Kevin F. Cassidy (Precambrian Research, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Adaptation to metal(loid)s in strain Mucilaginibacter rubeus P2 involves novel arsenic resistance genes and mechanisms - Yuanping Li; Yanshuang Yu; Xiaojun Yang; Aurora M. Pat-Espadas; Pablo Vinuesa; Martin Herzberg; Jian Chen; Barry P. Rosen; Renwei Feng; Christopher Rensing (Journal of Hazardous Materials, 2024)

Introduction of isotopically light barium from the Rainbow hydrothermal system into the deep Atlantic Ocean - Zhouling Zhang; Linbin Zhou; Xue-Gang Chen; Eric P. Achterberg; Yang Yu; Ed Hathorne; Zvi Steiner; Christopher Siebert; Martin Frank (Earth and Planetary Science Letters, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Hydrocarbon markers for assessing the influence of human activities in the tropical semi-arid region (Acaraú River, state of Ceará, Brazil) - Gabrielle M. Fernandes; Davi de A. Martins; Andre H.B. de Oliveira; Marcielly F.B. de Lima; Christopher M. Reddy; Robert K. Nelson; Rivelino M. Cavalcante (Chemosphere, 2023)

Restoring areas after a radioactive fallout: A multidisciplinary study on decontamination - Christopher Rääf; Johan Martinsson; Mats Eriksson; Jens Ewald; Reza G. Javid; Martin Hjellström; Mats Isaksson; Joel Rasmussen; Thomas Sterner; Robert Finck (Journal of Environmental Radioactivity, 2023)

Tradeoffs between timber and wildlife habitat quality increase with density in longleaf pine (Pinus palustris) plantations - Jacks M.T. Hausle; Jodi A. Forrester; Christopher E. Moorman; Melissa R. Martin (Forest Ecology and Management, 2023)

Systematic evidence on migrating and extractable food contact chemicals: Most chemicals detected in food contact materials are not listed for use - Birgit Geueke; Ksenia J. Groh; Maricel V. Maffini; Olwenn V. Martin; Justin M. Boucher; Yu-Ting Chiang; Frank Gwosdz; Phoenix Jieh; Christopher D. Kassotis; Paulina Łańska; John Peterson Myers; Alex Odermatt; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Ni nanoparticles on Co3O4 catalyze the reverse water–gas shift with 95 % CO selectivity at 300 °C - Brian Rutherford; Christopher Panaritis; Ergys Pahija; Martin Couillard; Bussaraporn Patarachao; Jalil Shadbahr; Farid Bensebaa; Gregory S. Patience; Daria C. Boffito (Fuel, 2023)

Field measurements of cable self-burial in a sandy marine environment - Christopher A. Unsworth; Martin J. Austin; Katrien J.J. Van Landeghem; Amelia J. Couldrey; Richard J.S. Whitehouse; Ben Lincoln; Siobhan Doole; Peter Worrall (Coastal Engineering, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Transfer of polychlorinated, polybrominated and mixed-halogenated dioxins, furans and biphenyls, polychlorinated naphthalenes and alkanes, polycyclic aromatic hydrocarbons and chlorobenzenes to the milk of dairy cattle from controlled ingestion of industrial and municipal bioresources recycled to agricultural land - Hannah Rigby; Alan Dowding; Alwyn Fernandes; David Humphries; Rupert G. Petch; Christopher K. Reynolds; Martin Rose; Stephen R. Smith (Science of The Total Environment, 2023)

Printability, texture, and sensory trade-offs for 3D printed potato with added proteins and lipids - Stefania Chirico Scheele; Martin Binks; Gordon Christopher; Farnaz Maleky; Paul F. Egan (Journal of Food Engineering, 2023)

Tidal barriers and fish – Impacts and remediation in the face of increasing demand for freshwater and climate change - Christopher M. Bice; Jeroen Huisman; Matthew E. Kimball; Martin Mallen-Cooper; Brenton P. Zampatti; Bronwyn M. Gillanders (Estuarine, Coastal and Shelf Science, 2023)

Avoiding investment in fossil fuel assets - Christopher A. Kennedy; Martin Sers; Michael I. Westphal (Journal of Industrial Ecology, 2023)
Reducing greenhouse gas emissions requires a transformation of capital assets in the economy, especially those for energy supply. This paper explores the hypothesis that economically efficient decarbonization occurs when the demand for fossil fuels declines at the same rate as their capital assets depreciate. In theory this means that new investments in fossil fuel assets are avoided, but without incurring stranded assets. We examine the practicality of this hypothesis using a biophysical economic model of the US energy supply system, with an example focused on impacts of electric vehicles on the petroleum supply chain. We specifically address two questions: (1) What rate of market penetration for electric vehicles is necessary to avoid investments in the petroleum‐related assets? (2) How do the costs of upstream capital assets change with the transformation to electric vehicles? High annual depreciation rates for oil refineries ( δ = 9.47%) and assets for crude oil extraction ( δ = 8.23%) have important impacts on results. To avoid new investment in oil refining assets through widespread electrification of light‐duty vehicles, the vehicle stock would need to be transformed in just 4 or 5 years. Under most scenarios, some petroleum pipelines will likely become stranded assets due to their low rate of depreciation ( δ = 2.48%). In some scenarios, additional investments in wind and solar power generation surpass oil and gas extraction for about 5 years during the transformation to electric vehicles. Once built, however, wind and solar capital assets last longer, as shown by their low rate of depreciation ( δ = 3.26%).

An interdisciplinary approach to the study of kiln firing: a case study from the Campus Galli open-air museum (southern Germany) - Silvia Amicone; Alisa Memmesheimer; Baptiste Solard; Shira Gur-Arieh; Martin Rogier; Awais Mohammed Qarni; Johannes Seidler; Paola Sconzo; Lars Heinze; Lionello F. Morandi; Tobias Kiemle; Christopher E. Miller; et al. (Archaeological and Anthropological Sciences, 2023)
Pottery kilns are a common feature in the archaeological record of different periods. However, these pyrotechnological installations are still seldom the target of interdisciplinary investigations. To fill this gap in our knowledge, an updraft kiln firing experiment was run at the Campus Galli open-air museum (southern Germany) by a team consisting of experimental archaeologists, material scientists, geoarchaeologists, and palaeobotanists. The entire process from the preparation of the raw materials to the firing and opening of the kiln was carefully recorded with a particular focus on the study of the raw materials used for pottery making, as well as on fuel usage. The temperatures were monitored by thermocouples placed at different positions in the combustion and firing chambers. In addition, thermocouples were installed within the kiln wall to measure the temperature distribution inside the structure itself. Unfired raw materials as well as controlled and experimentally thermally altered ceramic samples were then characterised with an integrated analysis including ceramic petrography, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and portable X-ray fluorescence (pXRF). Our work provides data about mineralogical and microstructural developments in both pottery kiln structures and the ceramics produced in this type of installations. This is helpful to discuss the limits and potential of various scientific analyses commonly used in ancient ceramic pyrotechnological studies. Overall, our work contributes to a better understanding of updraft kiln technology and offers guidelines on how to address the study of this type of pyrotechnological installations using interdisciplinary research strategies.

Forested watersheds provide the highest water quality among all land cover types, but the benefit of this ecosystem service depends on landscape context - Peter V. Caldwell; Katherine L. Martin; James M. Vose; Justin S. Baker; Travis W. Warziniack; Jennifer K. Costanza; Gregory E. Frey; Arpita Nehra; Christopher M. Mihiar (Science of The Total Environment, 2023)

Pedogenesis at the coastal arid-hyperarid transition deduced from a Late Quaternary chronosequence at Paposo, Atacama Desert - Janek Walk; Philipp Schulte; Melanie Bartz; Ariane Binnie; Martin Kehl; Ramona Mörchen; Xiaolei Sun; Georg Stauch; Christopher Tittmann; Roland Bol; Helmut Brückner; Frank Lehmkuhl (CATENA, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Forest disturbance and recovery in Peruvian Amazonia - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Mathieu Decuyper; Natalia Málaga; Patricia Durán Montesinos; Alexs Arana Olivos; Ricardo De la Cruz Paiva; Christopher Martius; Martin Herold (Global Change Biology, 2023)
Amazonian forests function as biomass and biodiversity reservoirs, contributing to climate change mitigation. While they continuously experience disturbance, the effect that disturbances have on biomass and biodiversity over time has not yet been assessed at a large scale. Here, we evaluate the degree of recent forest disturbance in Peruvian Amazonia and the effects that disturbance, environmental conditions and human use have on biomass and biodiversity in disturbed forests. We integrate tree‐level data on aboveground biomass (AGB) and species richness from 1840 forest plots from Peru's National Forest Inventory with remotely sensed monitoring of forest change dynamics, based on disturbances detected from Landsat‐derived Normalized Difference Moisture Index time series. Our results show a clear negative effect of disturbance intensity tree species richness. This effect was also observed on AGB and species richness recovery values towards undisturbed levels, as well as on the recovery of species composition towards undisturbed levels. Time since disturbance had a larger effect on AGB than on species richness. While time since disturbance has a positive effect on AGB, unexpectedly we found a small negative effect of time since disturbance on species richness. We estimate that roughly 15% of Peruvian Amazonian forests have experienced disturbance at least once since 1984, and that, following disturbance, have been increasing in AGB at a rate of 4.7 Mg ha −1 year −1 during the first 20 years. Furthermore, the positive effect of surrounding forest cover was evident for both AGB and its recovery towards undisturbed levels, as well as for species richness. There was a negative effect of forest accessibility on the recovery of species composition towards undisturbed levels. Moving forward, we recommend that forest‐based climate change mitigation endeavours consider forest disturbance through the integration of forest inventory data with remote sensing methods.

Deconstructing heterogeneity of replicative senescence in human mesenchymal stem cells at single cell resolution - Atefeh Taherian Fard; Hannah C. Leeson; Julio Aguado; Giovanni Pietrogrande; Dominique Power; Cecilia Gómez-Inclán; Huiwen Zheng; Christopher B. Nelson; Farhad Soheilmoghaddam; Nick Glass; Malindrie Dharmaratne; Ebony R. Watson; et al. (GeroScience, 2023)
Following prolonged cell division, mesenchymal stem cells enter replicative senescence, a state of permanent cell cycle arrest that constrains the use of this cell type in regenerative medicine applications and that in vivo substantially contributes to organismal ageing. Multiple cellular processes such as telomere dysfunction, DNA damage and oncogene activation are implicated in promoting replicative senescence, but whether mesenchymal stem cells enter different pre-senescent and senescent states has remained unclear. To address this knowledge gap, we subjected serially passaged human ESC-derived mesenchymal stem cells (esMSCs) to single cell profiling and single cell RNA-sequencing during their progressive entry into replicative senescence. We found that esMSC transitioned through newly identified pre-senescent cell states before entering into three different senescent cell states. By deconstructing this heterogeneity and temporally ordering these pre-senescent and senescent esMSC subpopulations into developmental trajectories, we identified markers and predicted drivers of these cell states. Regulatory networks that capture connections between genes at each timepoint demonstrated a loss of connectivity, and specific genes altered their gene expression distributions as cells entered senescence. Collectively, this data reconciles previous observations that identified different senescence programs within an individual cell type and should enable the design of novel senotherapeutic regimes that can overcome in vitro MSC expansion constraints or that can perhaps slow organismal ageing.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Anti-apoptotic genes and non-coding RNAs are potential outcome predictors for ulcerative colitis - Wei Meng; Kay-Martin Johnsen; Christopher G. Fenton; Jon Florholmen; Ruth H. Paulssen (Functional & Integrative Genomics, 2023)
Due to the lack of clinical, immunologic, genetic, and laboratory markers to predict remission in ulcerative colitis (UC) without relapse, there is no clear recommendation regarding withdrawal of therapy. Therefore, this study was to investigate if transcriptional analysis together with Cox survival analysis might be able to reveal molecular markers that are specific for remission duration and outcome. Mucosal biopsies from patients in remission with active treatment-naïve UC and healthy control subjects underwent whole-transcriptome RNA-seq. Principal component analysis (PCA) and Cox proportional hazards regression analysis were applied to the remission data concerning duration and status of patients. A randomly chosen remission sample set was used for validation of the applied methods and results. The analyses distinguished two different UC remission patient groups with respect to remission duration and outcome (relapse). Both groups showed that altered states of UC with quiescent microscopic disease activity are still present. The patient group with the longest remission duration and no relapse revealed specific and increased expression of antiapoptotic factors belonging to the MTRNR2-like gene family and non-coding RNAs. In summary, the expression of anti-apoptotic factors and non-coding RNAs may contribute to personalized medicine approaches in UC by improving patient stratification for different treatment regimens.

Successful intertidal colonization of the invasive macroalga Codium fragile near its equatorial/warm range limit in the South-East Pacific - David Jofré Madariaga; María Teresa González; Christopher Días Bórquez; Erasmo C. Macaya; Chris Harrod; Martin Thiel (Biological Invasions, 2023)

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

Multi-stage alteration at Nifty copper deposit resolved via accessory mineral dating and trace elements - Bruno V. Ribeiro; Christopher L. Kirkland; Michael I.H. Hartnady; Erin L. Martin; Emily West; Paul Polito (Precambrian Research, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Investigations of Plasma Metal Deposition (PMD) of 6061 and 7075 Aluminum Alloys for Aerospace and Automotive Applications - Christopher Wallis; Erich Neubauer; Michael Kitzmantel; Enrique Ariza Galván; Martin Bielik; Amir Horr; Mark Easton; Wolfgang Huebsch (BHM Berg- und Hüttenmännische Monatshefte, 2023)

Insights about levels and source appointment of petroleum hydrocarbons in Brazilian semi-arid coastal: baseline status assessment for ocean decade targets - Andre Henrique Barbosa de Oliveira; Gabrielle Melo Fernandes; Felipe Rodrigues dos Santos; Narelle Maia de Almeida; Tiago Rocha Nogueira; Diego de Quadros Melo; Laercio Lopes Martins; Rivelino Martins Cavalcante; Ronaldo Ferreira do Nascimento; Christopher Michael Reddy (Environmental Science and Pollution Research, 2023)

Estimation of survey efficiency and biomass for commercially important species from industry-based paired gear experiments - Timothy J. Miller; David E. Richardson; Philip J. Politis; Christopher D. Roebuck; John P. Manderson; Michael H. Martin; Andrew W. Jones (Fisheries Research, 2023)

Actinium and radium fluxes from the seabed in the northeast Pacific Basin - Nathaniel Kemnitz; Douglas E. Hammond; Paul Henderson; Emilie Le Roy; Matthew Charette; Willard Moore; Robert F. Anderson; Martin Q. Fleisher; Anne Leal; Erin Black; Christopher T. Hayes; Jess Adkins; et al. (Marine Chemistry, 2023)

Residual correlation and ensemble modelling to improve crop and grassland models - Renáta Sándor; Fiona Ehrhardt; Peter Grace; Sylvie Recous; Pete Smith; Val Snow; Jean-François Soussana; Bruno Basso; Arti Bhatia; Lorenzo Brilli; Jordi Doltra; Christopher D. Dorich; et al. (Environmental Modelling & Software, 2023)

Benthic-pelagic coupling and isotopic fractionation of barium in Kiel Bight, SW Baltic Sea - Florian Scholz; Jun Cheng; Zhouling Zhang; Paul Vosteen; Christopher Siebert; Martin Frank (Frontiers in Marine Science, 2023)
Barium (Ba) isotopes are a promising new tracer for riverine freshwater input to the ocean and marine biogeochemical cycling. However, many processes that affect Ba cycling at continental margins have not yet been investigated with respect to Ba isotope fractionation. Here, we present a comprehensive data set of Ba concentration and isotope data for water column, pore water and sediment samples from Kiel Bight, a seasonally stratified and hypoxic fjord in the southwestern Baltic Sea. The surface water Ba concentration and Ba isotope inventory of the water column can generally be explained by mixing of riverine freshwater and Atlantic seawater. However, the deep-water below the seasonal pycnocline (10 - 15 m water depth) is characterized by a pronounced positive Ba concentration anomaly (up to 915 nM) that is accompanied by a δ 138 Ba of ~+0.25 ‰, which is lighter than expected from the seawater-freshwater mixing line (Ba: 77 nM, δ 138 Ba: +0.32 ‰ at a salinity of 18). Pore water profiles indicate a Ba flux across the sediment-water interface, which contributes to the enrichment in isotopically light Ba in the deep-water. Pore waters of surface sediments and deep-waters are oversaturated with respect to barite. Therefore, barite dissolution is unlikely to account for the benthic Ba flux. Water column Ba concentrations closely correlate with those of the nutrients phosphate and silica, which are removed from surface waters by biological processes and recycled from the sediment by diffusion across the sediment-water interface. As nutrient-to-Ba ratios differ among sites and from those observed in open-marine systems, we propose that Ba is removed from surface waters by adsorption onto biogenic particles (rather than assimilation) and regenerated within surface sediments upon organic matter degradation. Pore water data for subsurface sediments in Kiel Bight indicate preferential transfer of isotopically heavy Ba into an authigenic phase during early diagenesis. Quantifying the burial flux associated with this authigenic Ba phase along continental margins could potentially help to settle the isotopic imbalance between known Ba source and sink fluxes in the ocean.

Using the Flocculation Index to optimise coagulant dosing during drinking water treatment - Mahmoud Khedher; John Awad; Erica Donner; Barbara Drigo; Rolando Fabris; Martin Harris; Kalan Braun; Christopher W.K. Chow (Journal of Water Process Engineering, 2023)

Citrobacter portucalensis Sb-2 contains a metalloid resistance determinant transmitted by Citrobacter phage Chris1 - Yanshuang Yu; Zhenchen Xie; Jigang Yang; Ruixiang Yang; Yuanping Li; Yongguan Zhu; Yanlin Zhao; Qiue Yang; Jichen Chen; Hend A. Alwathnani; Renwei Feng; Christopher Rensing; et al. (Journal of Hazardous Materials, 2023)

Breeding bird abundance and species diversity greatest in high-severity wildfire patches in central hardwood forests - Cathryn H. Greenberg; Christopher E. Moorman; Katherine J. Elliott; Katherine Martin; Mark Hopey; Peter V. Caldwell (Forest Ecology and Management, 2023)

Trace metal and sulfur cycling in a hydrothermally active arc volcano: deep-sea drilling of the Brothers volcano, Kermadec arc, New Zealand - Andrew J. Martin; John W. Jamieson; Cornel E. J. de Ronde; Susan E. Humphris; Iain McDonald; Graham D. Layne; Glenn Piercey; Christopher J. MacLeod (Mineralium Deposita, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

Average uranium bedrock concentration in Swedish municipalities predicts male lung cancer incidence rate when adjusted for smoking prevalence: Indication of a cumulative radon induced detriment - Christopher L. Rääf; Martin Tondel; Mats Isaksson; Robert Wålinder (Science of The Total Environment, 2023)

Stream degradation affects aquatic resource subsidies to riparian ground-dwelling spiders - Carmen Kowarik; Dominik Martin-Creuzburg; Kate L. Mathers; Christine Weber; Christopher T. Robinson (Science of The Total Environment, 2023)

Distal tephras along the SE European margin date powerful explosive eruptions from the Elbrus volcanic center (Greater Caucasus) - Vera Ponomareva; Maxim Portnyagin; Martin Danišík; Evgeny Konstantinov; Egor Zelenin; Nikolai Tkach; Folkmar Hauff; Axel K. Schmitt; Bjarne Friedrichs; Boris Romanyuk; Marcel Guillong; Christopher L. Kirkland; et al. (Quaternary Science Reviews, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Attractor Reconstruction for Quantifying the Arterial Pulse Wave Morphology During Device-Guided Slow Breathing - Carina Hörandtner; Martin Bachler; Walter Sehnert; Ines Mikisek; Thomas Mengden; Siegfried Wassertheurer; Christopher C. Mayer (Cardiovascular Engineering and Technology, 2022)
Attractor reconstruction is a new way to quantify the morphology of a cardiovascular waveform by plotting all data points in the three-dimensional phase space, generating a trajectory of overlapping loops. The aim of this study is to show the feasibility of an automatic approach to quantify pulse wave attractors from a device-guided breathing study, and to link attractor features to pulse waveform features. The recently developed feature extraction technique is applied to arterial pulse waveform data of 30 patients with treated hypertension. The patients performed a device-guided slow breathing exercise. The generated attractors were categorized into three different shapes: triangular attractors, bent attractors and attractors with overlapping arms. The average height of the attractors continuously and progressively dropped from 41.8 [35.4, 55.1] AU to 34.5 [25.4, 47.3] AU ( p < 0.001) during the breathing exercise. We have shown that the novel approach to quantify pulse wave attractors is feasible and can be used to detect changes in the morphology of arterial pulse waveforms. Device-guided slow breathing exercise has a shrinking effect on the average height of the attractors, which may indicate a reduction in blood pressure.

Accuracy, realism and general applicability of European forest models - Mats Mahnken; Maxime Cailleret; Alessio Collalti; Carlo Trotta; Corrado Biondo; Ettore D'Andrea; Daniela Dalmonech; Gina Marano; Annikki Mäkelä; Francesco Minunno; Mikko Peltoniemi; Volodymyr Trotsiuk; et al. (Global Change Biology, 2022)
Forest models are instrumental for understanding and projecting the impact of climate change on forests. A considerable number of forest models have been developed in the last decades. However, few systematic and comprehensive model comparisons have been performed in Europe that combine an evaluation of modelled carbon and water fluxes and forest structure. We evaluate 13 widely used, state‐of‐the‐art, stand‐scale forest models against field measurements of forest structure and eddy‐covariance data of carbon and water fluxes over multiple decades across an environmental gradient at nine typical European forest stands. We test the models' performance in three dimensions: accuracy of local predictions (agreement of modelled and observed annual data), realism of environmental responses (agreement of modelled and observed responses of daily gross primary productivity to temperature, radiation and vapour pressure deficit) and general applicability (proportion of European tree species covered). We find that multiple models are available that excel according to our three dimensions of model performance. For the accuracy of local predictions, variables related to forest structure have lower random and systematic errors than annual carbon and water flux variables. Moreover, the multi‐model ensemble mean provided overall more realistic daily productivity responses to environmental drivers across all sites than any single individual model. The general applicability of the models is high, as almost all models are currently able to cover Europe's common tree species. We show that forest models complement each other in their response to environmental drivers and that there are several cases in which individual models outperform the model ensemble. Our framework provides a first step to capturing essential differences between forest models that go beyond the most commonly used accuracy of predictions. Overall, this study provides a point of reference for future model work aimed at predicting climate impacts and supporting climate mitigation and adaptation measures in forests.

Hematological, biochemical, and biometric changes in Clarias gariepinus exposed to antipsychotic drug chlorpromazine - Martins Nnamdi Okpe; Christabel Chukwuebuka Eze; Hope Chinwe Ezinwa; Uduak Aletan; Henrietta Ijeoma Kelle; Maureen N. Chukwu; Martin Abdubala Okpanachi; Oscar Ifeanyi Aguzie; Christopher D. Nwani (Environmental Science and Pollution Research, 2022)

Removal of redox-sensitive Rubisco Activase does not alter Rubisco regulation in soybean - Christopher M. Harvey; Amanda P. Cavanagh; Sang Yeol Kim; David A. Wright; Ron G. Edquilang; Kayla S. Shreeves; Juan Alejandro Perdomo; Martin H. Spalding; Donald R. Ort; Carl J. Bernacchi; Steven C. Huber (Photosynthesis Research, 2022)

A role for the circadian transcription factor NPAS2 in the progressive loss of non-rapid eye movement sleep and increased arousal during fentanyl withdrawal in male mice - Mackenzie C. Gamble; Byron Chuan; Teresa Gallego-Martin; Micah A. Shelton; Stephanie Puig; Christopher P. O’Donnell; Ryan W. Logan (Psychopharmacology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The production of dissolved organic carbon by macroalgae and its consumption by marine bacteria: Implications for coastal ecosystems - Jack R. Hall; Gerli Albert; Isla M. Twigg; Federico Baltar; Christopher D. Hepburn; Georg Martin (Frontiers in Marine Science, 2022)
Through the fixation of large quantities of dissolved inorganic carbon (DIC), macroalgae facilitate the energetic foundation of highly productive coastal ecosystems. While the processes controlling photosynthesis and carbon fixation by macroalgae are well known, the fate of organic matter fixed by macroalgae is less well understood. This study quantified release rates of DOC by three ecologically significant Baltic macroalgae species: the perennial habitat forming Fucus vesiculosus and Furcellaria lumbricalis , and the seasonal fast-growing Ulva intestinalis , under both light and dark conditions. The released products were assessed using bacterial incubations whereby radiolabeled leucine was used to evaluate the uptake and lability of these products by marine heterotrophic bacteria. DOC was found to be released by both F. vesiculosus and U . intestinalis at rates of 0.27 mg C·h −1 under light and 0.13 mg C·h −1 per unit of dry mass under dark treatments, respectively, whereas F. lumbricalis DOC release was observed to be negligible under both light and dark. Our findings further validate previous hypotheses that factors such as photosynthetic activity are a primary driver behind DOC release and that DOC release is not an entirely passive process. Additionally, we reaffirm the need to relate a given species life characteristics and habitat in order to understand why DOC products are released. The consumption of macroalgae-derived DOC by heterotrophic bacteria reveals that released DOC is variable in its lability. After a period of 12 h and under maximum photosynthetic conditions, the release of DOC by F. vesiculosus and U . intestinalis achieved a peak rate of 219 µg C·L −1 ·day −1 and 214 µg C·L −1 ·day −1 for each gram of dry weight material, respectively, directly into the microbial loop via heterotrophic bacterial consumption. In contrast, F. lumbricalis ’ low rate of DOC release and the subsequent low bacterial consumption indicate that habitats dominated by this species have a reduced importance in the transfer energy via the microbial loop. These findings have implications for how we view carbon transfer within coastal food webs and highlight how changes in species composition and coverage may dramatically affect coastal ecosystem productivity through the microbial loop.

Editorial: Special issue on silicon at the root-soil interface - Martin J. Hodson; Christopher N. Guppy (Plant and Soil, 2022)

Some thoughts on silicon and carbon trade-offs in plants - Martin J. Hodson; Christopher N. Guppy (Plant and Soil, 2022)
In 1983, Raven suggested that silica could substitute for lignin or cellulose as a structural material in plants, and should be favoured because of its lower energetic costs. He then asked the question why more plants did not use silica for structural support. Raven’s idea eventually led to a whole series of investigations into the substitution of silicon for carbon in plants, so-called trade-offs. In this Opinion we offer some, hopefully helpful, thoughts on this research, and we attempt to answer Raven’s question. We conclude that more focus on the distribution of silicon and carbon at the cellular level is needed, and that we should be more careful to avoid teleological thinking.

Mineral-scale variation in the trace metal and sulfur isotope composition of pyrite: implications for metal and sulfur sources in mafic VMS deposits - Andrew J. Martin; Iain McDonald; John W. Jamieson; Gawen R. T. Jenkin; Katie A. McFall; Glenn Piercey; Christopher J. MacLeod; Graham D. Layne (Mineralium Deposita, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Modelling the Dispersion of Seafloor Massive Sulphide Mining Plumes in the Mid Atlantic Ridge Around the Azores - Telmo Morato; Manuela Juliano; Christopher K. Pham; Marina Carreiro-Silva; Inês Martins; Ana Colaço (Frontiers in Marine Science, 2022)
It is increasingly recognised that deep-sea mining of seafloor massive sulphides (SMS) could become an important source of mineral resources. These operations will remove the targeted substrate and produce potentially toxic plumes from in situ seabed excavation and from the return water pumped back down to the seafloor. However, the spatial extent of the impact of deep-sea mining is still uncertain because few field experiments and models of plume dispersion have been conducted. In this study, we used three-dimensional hydrodynamic models of the Azores region together with a theoretical commercial mining operation of polymetallic SMS to simulate the potential dispersal of plumes originating from different phases of mining operations, and to assess the magnitude of potential impacts. Although the model simulations presented here were subject to many caveats, they did reveal some important patterns. The model projected marked differences among sites making generalisations about plume-dispersal patterns in mid-ocean ridges difficult. Nevertheless, the models predicted large horizontal and vertical plume-dispersals above the thresholds adopted. Persistent plumes (temporal frequency >50%, i.e., 6 months out of 12 months) were projected to disperse an average linear distance of 10 to 20 km, cover an area of 17 to 150 km2, and extend more than 800 m in the water column. In fact, the model projected that plumes may disperse beyond the licensed mining areas, reach the flanks and summits of nearby topographic features, and extend into the bathypelagic, mesopelagic, and epipelagic environments. Modelled plume-dispersal overlaps with the predicted distribution of cold-water corals and with existing fishing activities. These potential impacts would be of particular concern in regions such as the Azores, where local populations are highly dependent on the sea for their livelihoods. The findings of this study are an important initial step towards understanding the nature and magnitude of deep-sea mining impacts in space and time.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Eurasian Holocene climate trends in transient coupled climate simulations and stable oxygen isotope records - CHRISTOPHER DANEK; PAUL GIERZ; SVETLANA S. KOSTROVA; PHILIP MEISTER; HANNO MEYER; MARTIN WERNER (Journal of Quaternary Science, 2022)
Transient simulations of the global fully coupled climate model COSMOS under realistic varying orbital and greenhouse gas forcings are systematically compared to diatom oxygen isotope ( ) records from Russian lakes with focus on Eurasian Holocene climate trends. The measured decrease and other temperature proxies are interpreted as large‐scale cooling throughout the Holocene while the model simulations are biased too warm, likely through missing radiative forcings. This large‐scale warm bias also dictates the modeled . Hence, at locations where the signs of model and proxy temperature/precipitation trends agree, measured and modeled trends show notable accordance. An increased temporal variability of modeled is linked to persistent atmospheric circulation patterns. Applying the transient forcings in an accelerated way (every 10th year only) yields a similar, yet weaker or delayed model response, especially in the ocean.

Cytotoxic and Radiosensitising Effects of a Novel Thioredoxin Reductase Inhibitor in Brain Cancers - Anqi Yao; Sarah J. Storr; Martyn Inman; Lucy Barwell; Christopher J. Moody; Stewart G. Martin (Molecular Neurobiology, 2022)
The thioredoxin (Trx) system, a key antioxidant pathway, represents an attractive target for cancer therapy. This study investigated the chemotherapeutic and radiosensitising effects of a novel Trx reductase (TrxR) inhibitor, IQ10, on brain cancer cells and the underlying mechanisms of action. Five brain cancer cell lines and a normal cell type were used. TrxR activity and expression were assessed by insulin reduction assay and Western blotting, respectively. IQ10 cytotoxicity was evaluated using growth curve, resazurin reduction and clonogenic assays. Radiosensitivity was examined using clonogenic assay. Reactive oxygen species levels were examined by flow cytometry and DNA damage assessed by immunofluorescence. Epithelial-mesenchymal transition (EMT)-related gene expression was examined by RT-PCR array. IQ10 significantly inhibited TrxR activity but did not affect Trx system protein expression in brain cancer cells. The drug exhibited potent anti-proliferative and cytotoxic effects against brain cancer cells under both normoxic and hypoxic conditions in both 2D and 3D systems, with IC 50 s in the low micromolar range. It was up to ~ 1000-fold more potent than temozolomide. IQ10 substantially sensitised various brain cancer cells to radiation, with such effect being due, in part, to functional inhibition of TrxR, making cells less able to deal with oxidative stress and leading to increased oxidative DNA damage. IQ10 significantly downregulated EMT-associated gene expression suggesting potential anti-invasive and antimetastatic properties. This study suggests that IQ10 is a potent anticancer agent and could be used as either a single agent or combined with radiation, to treat brain cancers.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Landscape Controls on Nutrient Stoichiometry Regulate Lake Primary Production at the Margin of the Greenland Ice Sheet - Clay Prater; Joanna E. Bullard; Christopher L. Osburn; Sarah L. Martin; Michael J. Watts; N. John Anderson (Ecosystems, 2022)
Global change is reshaping the physical environment and altering nutrient dynamics across the Arctic. These changes can affect the structure and function of biological communities and influence important climate-related feedbacks (for example, carbon (C) sequestration) in biogeochemical processing hot spots such as lakes. To understand how these ecosystems will respond in the future, this study examined recent (< 10 y) and long-term (1000 y) shifts in autotrophic production across paraglacial environmental gradients in SW Greenland. Contemporary lake temperatures and light levels increased with distance from the ice sheet, along with dissolved organic C (DOC) concentrations and total nitrogen:total phosphorus (TN:TP) ratios. Diatom production measured as biogenic silica accumulation rates (BSiARs) and diatom contribution to microbial communities declined across these gradients, while total production estimated using C accumulation rates and δ 13 C increased, indicating that autochthonous production and C burial are controlled by microbial competition and competitive displacement across physiochemical gradients in the region. Diatom production was generally low across lakes prior to the 1800’s AD but has risen 1.5–3× above background levels starting between 1750 and 1880 AD. These increases predate contemporary regional warming by 115–250 years, and temperature stimulation of primary production was inconsistent with paleorecords for ~ 90% of the last millennium. Instead, primary production appeared to be more strongly related to N and P availability, which differs considerably across the region due to lake landscape position, glacial activity and degree of atmospheric nutrient deposition. These results suggest that biological responses to enhanced nutrient supply could serve as important negative feedbacks to global change.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Siblicide in the city: the urban heat island accelerates sibling cannibalism in the black widow spider (Latrodectus hesperus) - Christopher de Tranaltes; Jessie Dunn; Jake M. Martin; J. Chadwick Johnson (Urban Ecosystems, 2022)

Monitoring a changing Arctic: Recent advancements in the study of sea ice microbial communities - Karley Campbell; Ilkka Matero; Christopher Bellas; Thomas Turpin-Jelfs; Philipp Anhaus; Martin Graeve; Francois Fripiat; Martyn Tranter; Jack Christopher Landy; Patricia Sanchez-Baracaldo; Eva Leu; Christian Katlein; et al. (Ambio, 2022)
Sea ice continues to decline across many regions of the Arctic, with remaining ice becoming increasingly younger and more dynamic. These changes alter the habitats of microbial life that live within the sea ice, which support healthy functioning of the marine ecosystem and provision of resources for human-consumption, in addition to influencing biogeochemical cycles (e.g. air–sea CO 2 exchange). With the susceptibility of sea ice ecosystems to climate change, there is a pressing need to fill knowledge gaps surrounding sea ice habitats and their microbial communities. Of fundamental importance to this goal is the development of new methodologies that permit effective study of them. Based on outcomes from the DiatomARCTIC project, this paper integrates existing knowledge with case studies to provide insight on how to best document sea ice microbial communities, which contributes to the sustainable use and protection of Arctic marine and coastal ecosystems in a time of environmental change.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Perspectives on Marine Data Science as a Blueprint for Emerging Data Science Disciplines - Maria-Theresia Verwega; Carola Trahms; Avan N. Antia; Thorsten Dickhaus; Enno Prigge; Martin H. U. Prinzler; Matthias Renz; Markus Schartau; Thomas Slawig; Christopher J. Somes; Arne Biastoch (Frontiers in Marine Science, 2021)
Earth System Sciences have been generating increasingly larger amounts of heterogeneous data in recent years. We identify the need to combine Earth System Sciences with Data Sciences, and give our perspective on how this could be accomplished within the sub-field of Marine Sciences. Marine data hold abundant information and insights that Data Science techniques can reveal. There is high demand and potential to combine skills and knowledge from Marine and Data Sciences to best take advantage of the vast amount of marine data. This can be accomplished by establishing Marine Data Science as a new research discipline. Marine Data Science is an interface science that applies Data Science tools to extract information, knowledge, and insights from the exponentially increasing body of marine data. Marine Data Scientists need to be trained Data Scientists with a broad basic understanding of Marine Sciences and expertise in knowledge transfer. Marine Data Science doctoral researchers need targeted training for these specific skills, a crucial component of which is co-supervision from both parental sciences. They also might face challenges of scientific recognition and lack of an established academic career path. In this paper, we, Marine and Data Scientists at different stages of their academic career, present perspectives to define Marine Data Science as a distinct discipline. We draw on experiences of a Doctoral Research School, MarDATA, dedicated to training a cohort of early career Marine Data Scientists. We characterize the methods of Marine Data Science as a toolbox including skills from their two parental sciences. All of these aim to analyze and interpret marine data, which build the foundation of Marine Data Science.

Projected future daily characteristics of African precipitation based on global (CMIP5, CMIP6) and regional (CORDEX, CORDEX-CORE) climate models - Alessandro Dosio; Martin W. Jury; Mansour Almazroui; Moetasim Ashfaq; Ismaila Diallo; Francois A. Engelbrecht; Nana A. B. Klutse; Christopher Lennard; Izidine Pinto; Mouhamadou B. Sylla; Alain T. Tamoffo (Climate Dynamics, 2021)
We provide an assessment of future daily characteristics of African precipitation by explicitly comparing the results of large ensembles of global (CMIP5, CMIP6) and regional (CORDEX, CORE) climate models, specifically highlighting the similarities and inconsistencies between them. Results for seasonal mean precipitation are not always consistent amongst ensembles: in particular, global models tend to project a wetter future compared to regional models, especially over the Eastern Sahel, Central and East Africa. However, results for other precipitation characteristics are more consistent. In general, all ensembles project an increase in maximum precipitation intensity during the wet season over all regions and emission scenarios (except the West Sahel for CORE) and a decrease in precipitation frequency (under the Representative Concentration Pathways RCP8.5) especially over the West Sahel, the Atlas region, southern central Africa, East Africa and southern Africa. Depending on the season, the length of dry spells is projected to increase consistently by all ensembles and for most (if not all) models over southern Africa, the Ethiopian highlands and the Atlas region. Discrepancies exist between global and regional models on the projected change in precipitation characteristics over specific regions and seasons. For instance, over the Eastern Sahel in July–August most global models show an increase in precipitation frequency but regional models project a robust decrease. Global and regional models also project an opposite sign in the change of the length of dry spells. CORE results show a marked drying over the regions affected by the West Africa monsoon throughout the year, accompanied by a decrease in mean precipitation intensity between May and July that is not present in the other ensembles. This enhanced drying may be related to specific physical mechanisms that are better resolved by the higher resolution models and highlights the importance of a process-based evaluation of the mechanisms controlling precipitation over the region.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Diminishing weed control exacerbates maize yield loss to adverse weather - Christopher A. Landau; Aaron G. Hager; Martin M. Williams (Global Change Biology, 2021)
Both weed interference and adverse weather can cause significant maize yield losses. However, most climate change projections on maize yields ignore the fact that weeds are widespread in maize production. Herein, we examine the effects of weed control and weather variability on maize yield loss due to weeds by using machine learning techniques on an expansive database of herbicide efficacy trials spanning 205 weather environments and 27 years. Late‐season control of all weed species was the most important driver of maize yield loss due to weeds according to multiple analyses. Average yield losses of 50% were observed with little to no weed control. Furthermore, when the highest levels of weed control were not achieved, drier, hotter conditions just before and during silking exacerbated maize yield losses due to weeds. Current climate predictions suggest much of the US maize‐growing regions will experience warmer, drier summers. This, coupled with the growing prevalence of herbicide resistance, increases the risk of maize yield loss due to weeds in the future without transformational change in weed management systems.

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Contrasting population manipulations reveal resource competition between two large marsupials: bare-nosed wombats and eastern grey kangaroos - Julie Tamura; Janeane Ingram; Alynn M. Martin; Christopher P. Burridge; Scott Carver (Oecologia, 2021)

Patterns of post‐drought recovery are strongly influenced by drought duration, frequency, post‐drought wetness, and bioclimatic setting - Tong Jiao; Christopher A. Williams; Martin G. De Kauwe; Christopher R. Schwalm; Belinda E. Medlyn (Global Change Biology, 2021)
Understanding vegetation recovery after drought is critical for projecting vegetation dynamics in future climates. From 1997 to 2009, Australia experienced a long‐lasting drought known as the Millennium Drought (MD), which led to widespread reductions in vegetation productivity. However, vegetation recovery post‐drought and its determinants remain unclear. This study leverages remote sensing products from different sources—fraction of absorbed photosynthetically active radiation (FPAR), based on optical data, and canopy density, derived from microwave data—and random forest algorithms to assess drought recovery over Australian natural vegetation during a 20‐year period centered on the MD. Post‐drought recovery was prevalent across the continent, with 6 out of 10 drought events seeing full recovery within about 6 months. Canopy density was slower to recover than leaf area seen in FPAR. The probability of full recovery was most strongly controlled by drought return interval, post‐drought hydrological condition, and drought length. Full recovery was seldom observed when drought events occurred at intervals of 3 months or less, and moderately dry (standardized water balance anomaly [SWBA] within [−1, −0.76]) post‐drought conditions resulted in less complete recovery than wet (SWBA > 0.3) post‐drought conditions. Press droughts, which are long term but not extreme, delayed recovery more than pulse droughts (short term but extreme) and led to a higher frequency of persistent decline. Following press droughts, the frequency of persistent decline differed little among biome types but peaked in semi‐arid regions across aridity levels. Forests and savanna required the longest recovery times for press drought, while grasslands were the slowest to recover for pulse drought. This study provides quantitative thresholds that could be used to improve the modeling of ecosystem dynamics post‐drought.

Approaches to regulating recreational fisheries: balancing biology with angler satisfaction - Martin C. Arostegui; Christopher M. Anderson; Rachel F. Benedict; Christopher Dailey; Evan A. Fiorenza; Abby R. Jahn (Reviews in Fish Biology and Fisheries, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Differential expression of miRNAs and functional role of mir-200a in high and low productivity CHO cells expressing an Fc fusion protein - Laura Bryan; Michael Henry; Niall Barron; Clair Gallagher; Ronan M. Kelly; Christopher C. Frye; Matthew D. Osborne; Martin Clynes; Paula Meleady (Biotechnology Letters, 2021)
Objectives We used miRNA and proteomic profiling to understand intracellular pathways that contribute to high and low specific productivity (Qp) phenotypes in CHO clonally derived cell lines (CDCLs) from the same cell line generation project. Results Differentially expressed (DE) miRNAs were identified which are predicted to target several proteins associated with protein folding. MiR-200a was found to have a number of predicted targets associated with the unfolded protein response (UPR) which were shown to have decreased expression in high Qp CDCLs and have no detected change at the mRNA level. MiR-200a overexpression in a CHO CDCL was found to increase recombinant protein titer by 1.2 fold and Qp by 1.8 fold. Conclusion These results may suggest a role for miR-200a in post-transcriptional regulation of the UPR, presenting miR-200a as a potential target for engineering industrially attractive CHO cell phenotypes.

Regional Reef Fish Survey Design and Scaling Using High-Resolution Mapping and Analysis - Gregory P. Asner; Nicholas Vaughn; Bryant W. Grady; Shawna A. Foo; Harish Anand; Rachel R. Carlson; Ethan Shafron; Christopher Teague; Roberta E. Martin (Frontiers in Marine Science, 2021)
Coral reefs are undergoing changes caused by coastal development, resource use, and climate change. The extent and rate of reef change demand robust and spatially explicit monitoring to support management and conservation decision-making. We developed and demonstrated an airborne-assisted approach to design and upscale field surveys of reef fish over an ecologically complex reef ecosystem along Hawai‘i Island. We also determined the minimal set of mapped variables, mapped reef strata, and field survey sites needed to meet three goals: (i) increase field survey efficiency, (ii) reduce field sampling costs, and (iii) ensure field sampling is geostatistically robust for upscaling to regional estimates of reef fish composition. Variability in reef habitat was best described by a combination of water depth, live coral and macroalgal cover, fine-scale reef rugosity, reef curvature, and latitude as a proxy for a regional climate-ecosystem gradient. In combination, these factors yielded 18 distinct reef habitats, or strata, throughout the study region, which subsequently required 117 field survey sites to quantify fish diversity and biomass with minimal uncertainty. The distribution of field sites was proportional to stratum size and the variation in benthic habitat properties within each stratum. Upscaled maps of reef survey data indicated that fish diversity is spatially more uniform than fish biomass, which was lowest in embayments and near land-based access points. Decreasing the number of field sites from 117 to 45 and 75 sites for diversity and biomass, respectively, resulted in a manageable increase of statistical uncertainty, but would still yield actionable trend data over time for the 60 km reef study region on Hawai‘i Island. Our findings suggest that high-resolution benthic mapping can be combined with stratified-random field sampling to generate spatially explicit estimates of fish diversity and biomass. Future expansions of the methodology can also incorporate temporal shifts in benthic composition to drive continuously evolving fish monitoring for sampling and upscaling. Doing so reduces field-based labor and costs while increasing the geostatistical power and ecological representativeness of field work.

A data-limited modeling approach for conserving connectivity in marine protected area networks - Christopher Blackford; Martin Krkošek; Marie-Josée Fortin (Marine Biology, 2021)

First Report of the Co-occurrence of Cylindrospermopsin, Nodularin and Microcystins in the Freshwaters of Lake Victoria, Tanzania - Geofrey J. Mchau; Revocatus Machunda; Martin Kimanya; Edna Makule; Yun Yun Gong; Emmanuel Mpolya; Julie P. Meneely; Christopher T. Elliott; Brett Greer (Exposure and Health, 2021)
There is a global concern regarding the increase of cyanotoxins in freshwater and their potential effects on human health. The existence of multiple toxins in freshwater can result in an increased risk of their bioaccumulation in humans from their ingestion through contaminated drinking water or recreational activities. This study, the first of its kind, was conducted to determine the occurrence of thirteen cyanotoxins namely; microcystins (-LA, -LF, -LR, -LY, -LW, -RR, -YR, -WR, dm MC-RR and dm MC-LR), anatoxin-a, nodularin and cylindrospermopsin in the freshwaters of Lake Victoria in Tanzania. A total of 23 sites were selected for water sampling. Samples were randomly collected from lakeshores ( n = 54), wells ( n = 66) and piped water ( n = 18) in two phases, February (dry season) and December (rainy season) 2018. Samples ( n = 138) were analysed using liquid chromatography mass spectrometry (UPLC-MS/MS). Cylindrospermopsin was the most abundant cyanotoxin detected in the lakeshores, with eight of the nine collection sites (89%) reporting cylindrospermopsin in phase I, compared to three out of nine (33%) in phase II. Microcystin congeners -RR, -LR and -YR were detected in phase I, with microcystins -RR and -LR detected in phase II. MC concentrations ranged from 0.003 to 0.007 μg/L for MC-RR, 0.01–0.013 μg/L for MC-LR and 0.004 to 0.01 μg/L for cylindrospermopsin, with nodularin reported once at a concentration of 0.01 μg/L. No cyanotoxins were detected in wells or in treated pipe water samples. The existence of multiple toxins in different collection sites may lead to synergistic effects and increase the toxicological risk to humans. This is the first study to report the presence of cylindrospermopsin and nodularin in the freshwaters of Lake Victoria.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Low-temperature silica-rich gold mineralization in mafic VMS systems: evidence from the Troodos ophiolite, Cyprus - Andrew J. Martin; Iain McDonald; Katie A. McFall; Christopher J. MacLeod; Hazel M. Prichard (Mineralium Deposita, 2021)

A common soil temperature threshold for the upper limit of alpine grasslands in European mountains - Sarah Bürli; Jean-Paul Theurillat; Manuela Winkler; Andrea Lamprecht; Harald Pauli; Christian Rixen; Klaus Steinbauer; Sonja Wipf; Otar Abdaladze; Christopher Andrews; Peter Barančok; José Luis Benito-Alonso; et al. (Alpine Botany, 2021)
While climatic research about treeline has a long history, the climatic conditions corresponding to the upper limit of closed alpine grasslands remain poorly understood. Here, we propose a climatic definition for this limit, the ‘grassline’, in analogy to the treeline, which is based on the growing season length and the soil temperature. Eighty-seven mountain summits across ten European mountain ranges, covering three biomes (boreal, temperate, Mediterranean), were inventoried as part of the GLORIA project. Vascular plant cover was estimated visually in 326 plots of 1 × 1 m. Soil temperatures were measured in situ for 2–7 years, from which the length of the growing season and mean temperature were derived. The climatic conditions corresponding to 40% plant cover were defined as the thresholds for alpine grassland. Closed vegetation was present in locations with a mean growing season soil temperature warmer than 4.9 °C, or a minimal growing season length of 85 days, with the growing season defined as encompassing days with daily mean ≥ 1 °C. Hence, the upper limit of closed grasslands was associated with a mean soil temperature close to that previously observed at the treeline, and in accordance with physiological thresholds to growth in vascular plants. In contrast to trees, whose canopy temperature is coupled with air temperature, small-stature alpine plants benefit from the soil warmed by solar radiation and consequently, they can grow at higher elevations. Since substrate stability is necessary for grasslands to occur at their climatic limit, the grassline rarely appears as a distinct linear feature.

From tree to architecture: how functional morphology of arborescence connects plant biology, evolution and physics - Anita Roth-Nebelsick; Tatiana Miranda; Martin Ebner; Wilfried Konrad; Christopher Traiser (Palaeobiodiversity and Palaeoenvironments, 2021)
Trees are the fundamental element of forest ecosystems, made possible by their mechanical qualities and their highly sophisticated conductive tissues. The evolution of trees, and thereby the evolution of forests, were ecologically transformative and affected climate and biogeochemical cycles fundamentally. Trees also offer a substantial amount of ecological niches for other organisms, such as epiphytes, creating a vast amount of habitats. During land plant evolution, a variety of different tree constructions evolved and their constructional principles are a subject of ongoing research. Understanding the “natural construction” of trees benefits strongly from methods and approaches from physics and engineering. Plant water transport is a good example for the ongoing demand for interdisciplinary efforts to unravel form-function relationships on vastly differing scales. Identification of the unique mechanism of water long-distance transport requires a solid basis of interfacial physics and thermodynamics. Studying tree functions by using theoretical approaches is, however, not a one-sided affair: The complex interrelationships between traits, functionality, trade-offs and phylogeny inspire engineers, physicists and architects until today.

Ensemble modelling, uncertainty and robust predictions of organic carbon in long‐term bare‐fallow soils - Roberta Farina; Renata Sándor; Mohamed Abdalla; Jorge Álvaro‐Fuentes; Luca Bechini; Martin A. Bolinder; Lorenzo Brilli; Claire Chenu; Hugues Clivot; Massimiliano De Antoni Migliorati; Claudia Di Bene; Christopher D. Dorich; et al. (Global Change Biology, 2021)
Simulation models represent soil organic carbon (SOC) dynamics in global carbon (C) cycle scenarios to support climate‐change studies. It is imperative to increase confidence in long‐term predictions of SOC dynamics by reducing the uncertainty in model estimates. We evaluated SOC simulated from an ensemble of 26 process‐based C models by comparing simulations to experimental data from seven long‐term bare‐fallow (vegetation‐free) plots at six sites: Denmark (two sites), France, Russia, Sweden and the United Kingdom. The decay of SOC in these plots has been monitored for decades since the last inputs of plant material, providing the opportunity to test decomposition without the continuous input of new organic material. The models were run independently over multi‐year simulation periods (from 28 to 80 years) in a blind test with no calibration (Bln) and with the following three calibration scenarios, each providing different levels of information and/or allowing different levels of model fitting: (a) calibrating decomposition parameters separately at each experimental site (Spe); (b) using a generic, knowledge‐based, parameterization applicable in the Central European region (Gen); and (c) using a combination of both (a) and (b) strategies (Mix). We addressed uncertainties from different modelling approaches with or without spin‐up initialization of SOC. Changes in the multi‐model median (MMM) of SOC were used as descriptors of the ensemble performance. On average across sites, Gen proved adequate in describing changes in SOC, with MMM equal to average SOC (and standard deviation) of 39.2 (±15.5) Mg C/ha compared to the observed mean of 36.0 (±19.7) Mg C/ha (last observed year), indicating sufficiently reliable SOC estimates. Moving to Mix (37.5 ± 16.7 Mg C/ha) and Spe (36.8 ± 19.8 Mg C/ha) provided only marginal gains in accuracy, but modellers would need to apply more knowledge and a greater calibration effort than in Gen, thereby limiting the wider applicability of models.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Urbanisation and Fishing Alter the Body Size and Functional Traits of a Key Fisheries Species - Ben L. Gilby; Andrew D. Olds; Felicity E. Hardcastle; Christopher J. Henderson; Rod M. Connolly; Tyson S. H. Martin; Tyson R. Jones; Paul S. Maxwell; Thomas A. Schlacher (Estuaries and Coasts, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Neurite outgrowth inhibitory levels of organophosphates induce tissue transglutaminase activity in differentiating N2a cells: evidence for covalent adduct formation - Ibtesam S. Almami; Maha A. Aldubayan; Shatha G. Felemban; Najiah Alyamani; Richard Howden; Alexander J. Robinson; Tom D. Z. Pearson; David Boocock; Alanood S. Algarni; A. Christopher Garner; Martin Griffin; Philip L. R. Bonner; et al. (Archives of Toxicology, 2020)
Organophosphate compounds (OPs) induce both acute and delayed neurotoxic effects, the latter of which is believed to involve their interaction with proteins other than acetylcholinesterase. However, few OP-binding proteins have been identified that may have a direct role in OP-induced delayed neurotoxicity. Given their ability to disrupt Ca 2+ homeostasis, a key aim of the current work was to investigate the effects of sub-lethal neurite outgrowth inhibitory levels of OPs on the Ca 2+ -dependent enzyme tissue transglutaminase (TG2). At 1–10 µM, the OPs phenyl saligenin phosphate (PSP) and chlorpyrifos oxon (CPO) had no effect cell viability but induced concentration-dependent decreases in neurite outgrowth in differentiating N2a neuroblastoma cells. The activity of TG2 increased in cell lysates of differentiating cells exposed for 24 h to PSP and chlorpyrifos oxon CPO (10 µM), as determined by biotin-cadaverine incorporation assays. Exposure to both OPs (3 and/or 10 µM) also enhanced in situ incorporation of the membrane permeable substrate biotin-X-cadaverine, as indicated by Western blot analysis of treated cell lysates probed with ExtrAvidin peroxidase and fluorescence microscopy of cell monolayers incubated with FITC-streptavidin. Both OPs (10 µM) stimulated the activity of human and mouse recombinant TG2 and covalent labelling of TG2 with dansylamine-labelled PSP was demonstrated by fluorescence imaging following SDS-PAGE. A number of TG2 substrates were tentatively identified by mass spectrometry, including cytoskeletal proteins, chaperones and proteins involved protein synthesis and gene regulation. We propose that the elevated TG2 activity observed is due to the formation of a novel covalent adduct between TG2 and OPs.

Contrasting signatures of introgression in North American box turtle ( Terrapene spp.) contact zones - Bradley T. Martin; Marlis R. Douglas; Tyler K. Chafin; John S. Placyk; Roger D. Birkhead; Christopher A. Phillips; Michael E. Douglas (Molecular Ecology, 2020)
Hybridization occurs differentially across the genome in a balancing act between selection and migration. With the unprecedented resolution of contemporary sequencing technologies, selection and migration can now be effectively quantified such that researchers can identify genetic elements involved in introgression. Furthermore, genomic patterns can now be associated with ecologically relevant phenotypes, given availability of annotated reference genomes. We do so in North American box turtles ( Terrapene ) by deciphering how selection affects hybrid zones at the interface of species boundaries and identifying genetic regions potentially under selection that may relate to thermal adaptations. Such genes may impact physiological pathways involved in temperature‐dependent sex determination, immune system functioning and hypoxia tolerance. We contrasted these patterns across inter‐ and intraspecific hybrid zones that differ temporally and biogeographically. We demonstrate hybridization is broadly apparent in Terrapene , but with observed genomic cline patterns corresponding to species boundaries at loci potentially associated with thermal adaptation. These loci display signatures of directional introgression within intraspecific boundaries, despite a genome‐wide selective trend against intergrades. In contrast, outlier loci for interspecific comparisons exhibited evidence of being under selection against hybrids. Importantly, adaptations coinciding with species boundaries in Terrapene overlap with climatic boundaries and highlight the vulnerability of these terrestrial ectotherms to anthropogenic pressures.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Comparing Water Level Estimation in Coastal and Shelf Seas From Satellite Altimetry and Numerical Models - Julia Rulent; Francisco M. Calafat; Christopher J. Banks; Lucy May Bricheno; Christine Gommenginger; J. A. Mattias Green; Ivan D. Haigh; Huw Lewis; Adrien C. H. Martin (Frontiers in Marine Science, 2020)

Commentary: Brightness of the Night Sky Affects Loggerhead (Caretta caretta) Sea Turtle Hatchling Misorientation but Not Nest Site Selection - Travis Longcore; Dan Duriscoe; Martin Aubé; Andreas Jechow; Christopher C. M. Kyba; Kellie L. Pendoley (Frontiers in Marine Science, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Could ocean acidification influence epiphytism? A comparison of carbon-use strategies between Fucus vesiculosus and its epiphytes in the Baltic Sea - Gerli Albert; Christopher D. Hepburn; Liina Pajusalu; Tiina Paalme; Daniel W. Pritchard; Georg Martin (Journal of Applied Phycology, 2020)

Ocean acidification may threaten a unique seaweed community and associated industry in the Baltic Sea - Liina Pajusalu; Gerli Albert; Evangeline Fachon; Christopher D. Hepburn; Jonne Kotta; Kiran Liversage; Tiina Paalme; Anneliis Peterson; Daniel W. Pritchard; Arno Põllumäe; Kaire Torn; Georg Martin (Journal of Applied Phycology, 2020)

Ecological divergence in sympatry causes gene misexpression in hybrids - Joseph A. McGirr; Christopher H. Martin (Molecular Ecology, 2020)
Ecological speciation occurs when reproductive isolation evolves as a byproduct of adaptive divergence between populations. Selection favouring gene regulatory divergence between species could result in transgressive levels of gene expression in F1 hybrids that may lower hybrid fitness. We combined 58 resequenced genomes with 124 transcriptomes to identify patterns of hybrid gene misexpression that may be driven by adaptive regulatory divergence within a young radiation of Cyprinodon pupfishes, which consists of a dietary generalist and two trophic specialists—a molluscivore and a scale‐eater. We found more differential gene expression between closely related sympatric specialists than between allopatric generalist populations separated by 1,000 km. Intriguingly, 9.6% of genes that were differentially expressed between sympatric species were also misexpressed in F1 hybrids. A subset of these genes were in highly differentiated genomic regions and enriched for functions important for trophic specialization, including head, muscle and brain development. These regions also included genes that showed evidence of hard selective sweeps and were significantly associated with oral jaw length—the most rapidly diversifying skeletal trait in this radiation. Our results indicate that divergent ecological selection in sympatry can contribute to hybrid gene misexpression which may act as a reproductive barrier between nascent species.

Oral shelling within an adaptive radiation of pupfishes: Testing the adaptive function of a novel nasal protrusion and behavioural preference - Michelle E. St. John; Kristi E. Dixon; Christopher H. Martin (Journal of Fish Biology, 2020)
Dietary specialization on hard prey items, such as mollusks and crustaceans, is commonly observed in a diverse array of fish species. Many fish consume these types of prey by crushing the shell to consume the soft tissue within, but a few fishes extricate the soft tissue without breaking the shell using a method known as oral shelling. Oral shelling involves pulling a mollusc from its shell and it may be a way to subvert an otherwise insurmountable shell defence. However, the biomechanical requirements and potential adaptations for oral shelling are unknown. Here, we test the hypothesis that a novel nasal protrusion is an adaptation for oral shelling in the durophagous pupfish ( Cyprinodon brontotheroides ). We first demonstrate oral shelling in this species and then predict that a larger nasal protrusion would allow pupfish to consume larger snails. Durophagous pupfish are found within an endemic radiation of pupfish on San Salvador Island, Bahamas. We took advantage of closely related sympatric species and outgroups to test: (a) whether durophagous pupfish shell and consume more snails than other species, (b) if F1 and F2 durophagous hybrids consume similar amounts of snails as purebred durophagous pupfish, and (c) if nasal protrusion size in parental and hybrid populations increases the maximum size of consumed snails. We found that durophagous pupfish and their hybrids consumed the most snails, but did not find a strong association between nasal protrusion size and maximum snail size consumed within the parental or F2 hybrid population, suggesting that the size of their novel nasal protrusion does not provide a major benefit in oral shelling. Instead, we suggest that the nasal protrusion may increase feeding efficiency, act as a sensory organ, or is a sexually selected trait, and that a strong feeding preference may be most important for oral shelling.

Founder Effects of Spinocerebellar Ataxias in the American Continents and the Caribbean - Roberto Rodríguez-Labrada; Ana Carolina Martins; Jonathan J. Magaña; Yaimeé Vazquez-Mojena; Jacqueline Medrano-Montero; Juan Fernandez-Ruíz; Bulmaro Cisneros; Helio Teive; Karen N. McFarland; Maria Luiza Saraiva-Pereira; César M. Cerecedo-Zapata; Christopher M. Gomez; et al. (The Cerebellum, 2020)

Fetal Transcatheter Trileaflet Heart Valve Hemodynamics: Implications of Scaling on Valve Mechanics and Turbulence - Hoda Hatoum; Shelley Gooden; Megan Heitkemper; Kevin M. Blum; Jason Zakko; Martin Bocks; Tai Yi; Yen-Lin Wu; Yadong Wang; Christopher K. Breuer; Lakshmi Prasad Dasi (Annals of Biomedical Engineering, 2020)

Towards resolving the phosphorus chaos created by food systems - Paul J. A. Withers; Kirsty G. Forber; Christopher Lyon; Shane Rothwell; Donnacha G. Doody; Helen P. Jarvie; Julia Martin-Ortega; Brent Jacobs; Dana Cordell; Myles Patton; Miller A. Camargo-Valero; Rachel Cassidy (Ambio, 2020)
The chaotic distribution and dispersal of phosphorus (P) used in food systems (defined here as disorderly disruptions to the P cycle) is harming our environment beyond acceptable limits. An analysis of P stores and flows across Europe in 2005 showed that high fertiliser P inputs relative to productive outputs was driving low system P efficiency (38 % overall). Regional P imbalance (P surplus) and system P losses were highly correlated to total system P inputs and animal densities, causing unnecessary P accumulation in soils and rivers. Reducing regional P surpluses to zero increased system P efficiency (+ 16 %) and decreased total P losses by 35 %, but required a reduction in system P inputs of ca. 40 %, largely as fertiliser. We discuss transdisciplinary and transformative solutions that tackle the P chaos by collective stakeholder actions across the entire food value chain. Lowering system P demand and better regional governance of P resources appear necessary for more efficient and sustainable food systems.

Seasonal variation in Arctic marine mammal acoustic detection in the northern Bering Sea - Emily Chou; Ricardo Antunes; Stephanie Sardelis; Kathleen M. Stafford; Leigh West; Christopher Spagnoli; Brandon L. Southall; Martin Robards; Howard C. Rosenbaum (Marine Mammal Science, 2020)
Declines in Arctic sea ice cover are influencing the distribution of protected endemic marine mammals, many of which are important for local Indigenous Peoples, and increasing the presence of potentially disruptive industrial activities. Due to increasing conservation concerns, we conducted the first year‐round acoustic monitoring of waters off Gambell and Savoonga (St. Lawrence Island, Alaska), and in the Bering Strait to quantify vocalizing presence of bowhead whales, belugas, walruses, bearded seals, and ribbon seals. Bottom‐mounted archival acoustic recorders collected data for up to 10 months per deployment between 2012 and 2016. Spectrograms were analyzed for species‐typical vocalizations, and daily detection rates and presence/absence were calculated. Generalized additive models were used to model call presence as a function of time‐of‐year, sea surface temperature, and sea ice concentration. We identified seasonality in call presence for all species, corroborating previous acoustic and distribution studies, and identified finer‐scale spatiotemporal distribution via occurrence of call presence between different monitoring sites. Time‐of‐year was the strongest significant effect on call presence for all species. These data provide important information on Arctic endemic species' spatiotemporal distributions in biologically and culturally important areas within a rapidly changing Arctic region.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Correction to: Xenopus LAP2β protein knockdown affects location of Lamin B and nucleoporins and has effect on assembly of cell nucleus and cell viability - Magda Dubińska-Magiera; Magdalena Chmielewska; Katarzyna Kozioł; Magdalena Machowska; Christopher J. Hutchison; Martin W. Goldberg; Ryszard Rzepecki (Protoplasma, 2020)

Zircon oxygen and hafnium isotope decoupling during regional metamorphism: implications for the generation of low δ18O magmas - Michael I. H. Hartnady; Christopher L. Kirkland; Laure Martin; Chris Clark; R. Hugh Smithies; Catherine V. Spaggiari (Contributions to Mineralogy and Petrology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Mechanistic Insights into Factor VIII Immune Tolerance Induction via Prenatal Cell Therapy in Hemophilia A - Martin Rodriguez; Christopher D. Porada; Graça Almeida-Porada (Current Stem Cell Reports, 2019)

Understanding Public Views on a Dam Construction Boom: the Role of Values - Christopher Schulz; Julia Martin-Ortega; Klaus Glenk (Water Resources Management, 2019)
Large numbers of dams for hydroelectric power production are currently planned or under construction in many areas around the world. While positive and negative social and environmental impacts of dams are increasingly well understood, little is known about attitudes of the general public towards dams, even though benefits to wider society are often cited to legitimise their construction. In Brazil’s Upper Paraguay River Basin, more than 100 mostly small-scale hydropower dams are planned or under construction in what can be considered a regional dam construction boom. Here we analyse public preferences for strategies to manage dam impacts in the area by investigating the value base that underpins such preferences, drawing on the recently proposed Value Landscapes Approach as our theoretical framework and data from a large representative household survey ( N = 1067). We find that contrasting attitudes towards dams, expressed in preferences for economically or ecologically oriented water policies are informed by opposing underlying value landscapes, that is, groups of closely related fundamental, governance-related, and assigned (water) values. While such tensions between opposing values can never be fully eliminated, our research nevertheless gives insights to policy-makers seeking to minimise value conflict and to improve the political legitimacy of public decision-making on dam construction. Moreover, we find that a majority of members of the general public would prefer concentrating dam construction on some rivers while keeping others free-flowing, with direct implications for ecosystems and inland fisheries. This finding may guide policy-makers wishing to develop publicly supported water resources management strategies.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Passive acoustic monitoring predicts daily variation in North Atlantic right whale presence and relative abundance in Roseway Basin, Canada - Delphine Durette‐Morin; Kimberley T. A. Davies; Hansen D. Johnson; Moira W. Brown; Hilary Moors‐Murphy; Bruce Martin; Christopher T. Taggart (Marine Mammal Science, 2019)
North Atlantic right whale monitoring in Roseway Basin, Canada, is primarily based on short‐term ( n = 23 d) implied a 40% decline in right whale presence during 2014–2015 relative to 2004–2005, PAM data ( n = 211 d) showed right whales were present between 71%–85% of survey days throughout all years analyzed. We demonstrate that PAM is a useful tool to extend periods of right whale monitoring, especially in areas where visual monitoring efforts may be limited.

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Stephen G. Penny; Santha Akella; Magdalena A. Balmaseda; Philip Browne; James A. Carton; Matthieu Chevallier; Francois Counillon; Catia Domingues; Sergey Frolov; Patrick Heimbach; Patrick Hogan; Ibrahim Hoteit; et al. (Frontiers in Marine Science, 2019)

Substantial increase in minimum lake surface temperatures under climate change - R. Iestyn Woolway; Gesa A. Weyhenmeyer; Martin Schmid; Martin T. Dokulil; Elvira de Eyto; Stephen C. Maberly; Linda May; Christopher J. Merchant (Climatic Change, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

What is marine justice? - Jennifer A. Martin; Summer Gray; Eréndira Aceves-Bueno; Peter Alagona; Tammy L. Elwell; Angela Garcia; Zach Horton; David Lopez-Carr; Jessica Marter-Kenyon; Karly Marie Miller; Christopher Severen; Teresa Shewry; et al. (Journal of Environmental Studies and Sciences, 2019)

Intestinal nerve cell injury occurs prior to insulin resistance in female mice ingesting a high-fat diet - Yvonne Nyavor; Rachel Estill; Hannah Edwards; Hailey Ogden; Kaila Heideman; Kiefer Starks; Christopher Miller; George May; Lance Flesch; John McMillan; Martin Gericke; Larry Forney; et al. (Cell and Tissue Research, 2019)

Molecular Adaptations in the Rat Dorsal Striatum and Hippocampus Following Abstinence-Induced Incubation of Drug Seeking After Escalated Oxycodone Self-Administration - Christopher A. Blackwood; Reece Hoerle; Michael Leary; Jennifer Schroeder; Martin O. Job; Michael T. McCoy; Bruce Ladenheim; Subramaniam Jayanthi; Jean Lud Cadet (Molecular Neurobiology, 2019)

SN-CAST: seismic network capability assessment software tool for regional networks-examples from Ireland - Martin Möllhoff; Christopher J. Bean; Brian J. Baptie (Journal of Seismology, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

Regionalization in LCA: current status in concepts, software and databases—69th LCA forum, Swiss Federal Institute of Technology, Zurich, 13 September, 2018 - Rolf Frischknecht; Stephan Pfister; Jonas Bunsen; Adrian Haas; Josef Känzig; Martin Kilga; Jens Lansche; Manuele Margni; Christopher Mutel; Jürgen Reinhard; Philippe Stolz; Rosalie van Zelm; et al. (The International Journal of Life Cycle Assessment, 2019)

Bank erosion in an Andean páramo river system: Implications for hydro-development and carbon dynamics in the neotropical Andes - Derek J Martin; Christopher Ely; Beverley C Wemple (Journal of Mountain Science, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Speciation in sympatry with ongoing secondary gene flow and a potential olfactory trigger in a radiation of Cameroon cichlids - Jelmer W. Poelstra; Emilie J. Richards; Christopher H. Martin (Molecular Ecology, 2018)
The process of sympatric speciation in nature remains a fundamental unsolved problem. Cameroon crater lake cichlid radiations were long regarded as one of the most compelling examples; however, recent work showed that their origins were more complex than a single colonization event followed by isolation. Here, we performed a detailed investigation of the speciation history of a radiation of Coptodon cichlids from Lake Ejagham, Cameroon, using whole‐genome sequencing data. The existence of the Lake Ejagham Coptodon radiation is remarkable as this 0.5 km 2 lake offers limited scope for divergence across a shallow depth gradient, disruptive selection is currently weak, and the species are sexually monochromatic. We infer that Lake Ejagham was colonized by Coptodon cichlids soon after its formation 9,000 years ago, yet speciation occurred only in the last 1,000–2,000 years. We show that secondary gene flow from a nearby riverine species has been ongoing, into ancestral as well as extant lineages, and we identify and date river‐to‐lake admixture blocks. One block contains a cluster of olfactory receptor genes that introgressed near the time of the first speciation event and coincides with a higher overall rate of admixture. Olfactory signalling is a key component of mate choice and species recognition in cichlids. A functional role for this introgression event is consistent with previous findings that sexual isolation appears much stronger than ecological isolation in Ejagham Coptodon . We conclude that speciation in this radiation took place in sympatry, yet may have benefited from ongoing riverine gene flow.

Quantifying branch architecture of tropical trees using terrestrial LiDAR and 3D modelling - Alvaro Lau; Lisa Patrick Bentley; Christopher Martius; Alexander Shenkin; Harm Bartholomeus; Pasi Raumonen; Yadvinder Malhi; Tobias Jackson; Martin Herold (Trees, 2018)

Insectivorous birds consume an estimated 400–500 million tons of prey annually - Martin Nyffeler; Çağan H. Şekercioğlu; Christopher J. Whelan (The Science of Nature, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Prediction of enteric methane production, yield, and intensity in dairy cattle using an intercontinental database - Mutian Niu; Ermias Kebreab; Alexander N. Hristov; Joonpyo Oh; Claudia Arndt; André Bannink; Ali R. Bayat; André F. Brito; Tommy Boland; David Casper; Les A. Crompton; Jan Dijkstra; et al. (Global Change Biology, 2018)
Enteric methane ( CH 4 ) production from cattle contributes to global greenhouse gas emissions. Measurement of enteric CH 4 is complex, expensive, and impractical at large scales; therefore, models are commonly used to predict CH 4 production. However, building robust prediction models requires extensive data from animals under different management systems worldwide. The objectives of this study were to (1) collate a global database of enteric CH 4 production from individual lactating dairy cattle; (2) determine the availability of key variables for predicting enteric CH 4 production (g/day per cow), yield [g/kg dry matter intake ( DMI )], and intensity (g/kg energy corrected milk) and their respective relationships; (3) develop intercontinental and regional models and cross‐validate their performance; and (4) assess the trade‐off between availability of on‐farm inputs and CH 4 prediction accuracy. The intercontinental database covered Europe ( EU ), the United States ( US ), and Australia ( AU ). A sequential approach was taken by incrementally adding key variables to develop models with increasing complexity. Methane emissions were predicted by fitting linear mixed models. Within model categories, an intercontinental model with the most available independent variables performed best with root mean square prediction error ( RMSPE ) as a percentage of mean observed value of 16.6%, 14.7%, and 19.8% for intercontinental, EU , and United States regions, respectively. Less complex models requiring only DMI had predictive ability comparable to complex models. Enteric CH 4 production, yield, and intensity prediction models developed on an intercontinental basis had similar performance across regions, however, intercepts and slopes were different with implications for prediction. Revised CH 4 emission conversion factors for specific regions are required to improve CH 4 production estimates in national inventories. In conclusion, information on DMI is required for good prediction, and other factors such as dietary neutral detergent fiber ( NDF ) concentration, improve the prediction. For enteric CH 4 yield and intensity prediction, information on milk yield and composition is required for better estimation.

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Rare Earth Elements Geochemistry and Nd Isotopes in the Mississippi River and Gulf of Mexico Mixing Zone - Segun B. Adebayo; Minming Cui; Travis Hong; Christopher D. White; Ellen E. Martin; Karen H. Johannesson (Frontiers in Marine Science, 2018)

Plant-associated bacteria mitigate drought stress in soybean - Samuel Julio Martins; Geisiane Alves Rocha; Hyrandir Cabral de Melo; Raphaela de Castro Georg; Cirano José Ulhôa; Érico de Campos Dianese; Leticia Harumi Oshiquiri; Marcos Gomes da Cunha; Mara Rúbia da Rocha; Leila Garcês de Araújo; Karina Santana Vaz; Christopher A. Dunlap (Environmental Science and Pollution Research, 2018)

YcfDRM is a thermophilic oxygen-dependent ribosomal protein uL16 oxygenase - Rok Sekirnik; Sarah E. Wilkins; Jacob Bush; Hanna Tarhonskaya; Martin Münzel; Aayan Hussein; Emily Flashman; Shabaz Mohammed; Michael A. McDonough; Christoph Loenarz; Christopher J. Schofield (Extremophiles, 2018)

Performance assessment of a single-layer moisture store-and-release cover system at a mine waste rock pile in a seasonally humid region (Nova Scotia, Canada) - Christopher Power; Murugan Ramasamy; Martin Mkandawire (Environmental Monitoring and Assessment, 2018)

Mutualism between Klebsiella SGM 81 and Dianthus caryophyllus in modulating root plasticity and rhizospheric bacterial density - Shraddha Gang; Meenu Saraf; Christopher J. Waite; Martin Buck; Jörg Schumacher (Plant and Soil, 2018)

Stress-induced variation in host susceptibility to parasitic freshwater mussel larvae - Karel Douda; Michael Martin; Elizabeth Glidewell; Christopher Barnhart (Hydrobiologia, 2018)

New evidence for the recent divergence of Devil's Hole pupfish and the plausibility of elevated mutation rates in endangered taxa - Christopher H. Martin; Sebastian Höhna (Molecular Ecology, 2018)
Sağlam et al. recently argued that the Devil's Hole pupfish ( Cyprinodon diabolis ), a conservation icon with the smallest known species range, was isolated 60 kya based on a new genomic data set. If true, this would be a radically long timescale for any species to persist at population sizes C. diabolis , ranging from 6.2 to 19.9 kya, overlapping with our previous phylogenetic divergence time estimates of 2.5–6.5 kya. There are many reasons to suspect an even younger age and higher mutation rate in C. diabolis , as we previously estimated, due to their high metabolism, small adult size, small population size and severe environmental stressors. In conclusion, our results highlight the need for measuring mutation rate in this fascinating species and suggest that the ages of endangered taxa present in small, isolated populations may frequently be overestimated.

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Towards physiologically meaningful water‐use efficiency estimates from eddy covariance data - Jürgen Knauer; Sönke Zaehle; Belinda E. Medlyn; Markus Reichstein; Christopher A. Williams; Mirco Migliavacca; Martin G. De Kauwe; Christiane Werner; Claudia Keitel; Pasi Kolari; Jean‐Marc Limousin; Maj‐Lena Linderson (Global Change Biology, 2018)
Intrinsic water‐use efficiency ( iWUE ) characterizes the physiological control on the simultaneous exchange of water and carbon dioxide in terrestrial ecosystems. Knowledge of iWUE is commonly gained from leaf‐level gas exchange measurements, which are inevitably restricted in their spatial and temporal coverage. Flux measurements based on the eddy covariance ( EC ) technique can overcome these limitations, as they provide continuous and long‐term records of carbon and water fluxes at the ecosystem scale. However, vegetation gas exchange parameters derived from EC data are subject to scale‐dependent and method‐specific uncertainties that compromise their ecophysiological interpretation as well as their comparability among ecosystems and across spatial scales. Here, we use estimates of canopy conductance and gross primary productivity ( GPP ) derived from EC data to calculate a measure of iWUE ( G 1 , “stomatal slope”) at the ecosystem level at six sites comprising tropical, Mediterranean, temperate, and boreal forests. We assess the following six mechanisms potentially causing discrepancies between leaf and ecosystem‐level estimates of G 1 : (i) non‐transpirational water fluxes; (ii) aerodynamic conductance; (iii) meteorological deviations between measurement height and canopy surface; (iv) energy balance non‐closure; (v) uncertainties in net ecosystem exchange partitioning; and (vi) physiological within‐canopy gradients. Our results demonstrate that an unclosed energy balance caused the largest uncertainties, in particular if it was associated with erroneous latent heat flux estimates. The effect of aerodynamic conductance on G 1 was sufficiently captured with a simple representation. G 1 was found to be less sensitive to meteorological deviations between canopy surface and measurement height and, given that data are appropriately filtered, to non‐transpirational water fluxes. Uncertainties in the derived GPP and physiological within‐canopy gradients and their implications for parameter estimates at leaf and ecosystem level are discussed. Our results highlight the importance of adequately considering the sources of uncertainty outlined here when EC ‐derived water‐use efficiency is interpreted in an ecophysiological context.

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Concomitant external pneumatic compression treatment with consecutive days of high intensity interval training reduces markers of proteolysis - Cody T. Haun; Michael D. Roberts; Matthew A. Romero; Shelby C. Osburn; James C. Healy; Angelique N. Moore; Christopher B. Mobley; Paul A. Roberson; Wesley C. Kephart; Petey W. Mumford; Michael D. Goodlett; David D. Pascoe; et al. (European Journal of Applied Physiology, 2017)

Five-year performance monitoring of a high-density polyethylene (HDPE) cover system at a reclaimed mine waste rock pile in the Sydney Coalfield (Nova Scotia, Canada) - Christopher Power; Murugan Ramasamy; Devin MacAskill; Joseph Shea; Joseph MacPhee; David Mayich; Fred Baechler; Martin Mkandawire (Environmental Science and Pollution Research, 2017)

Assessing trait‐based scaling theory in tropical forests spanning a broad temperature gradient - Brian J. Enquist; Lisa Patrick Bentley; Alexander Shenkin; Brian Maitner; Van Savage; Sean Michaletz; Benjamin Blonder; Vanessa Buzzard; Tatiana Erika Boza Espinoza; William Farfan‐Rios; Christopher E. Doughty; Gregory R. Goldsmith; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical elevation gradients are natural laboratories to assess how changing climate can influence tropical forests. However, there is a need for theory and integrated data collection to scale from traits to ecosystems. We assess predictions of a novel trait‐based scaling theory, including whether observed shifts in forest traits across a broad tropical temperature gradient are consistent with local phenotypic optima and adaptive compensation for temperature. Location An elevation gradient spanning 3,300 m and consisting of thousands of tropical tree trait measures taken from 16 1‐ha tropical forest plots in southern Perú, where gross and net primary productivity (GPP and NPP) were measured. Time period April to November 2013. Major taxa studied Plants; tropical trees. Methods We developed theory to scale from traits to communities and ecosystems and tested several predictions. We assessed the covariation between climate, traits, biomass and GPP and NPP. We measured multiple traits linked to variation in tree growth and assessed their frequency distributions within and across the elevation gradient. We paired these trait measures across individuals within 16 forests with simultaneous measures of ecosystem net and gross primary productivity. Results Consistent with theory, variation in forest NPP and GPP primarily scaled with forest biomass, but the secondary effect of temperature on productivity was much less than expected. This weak temperature dependence appears to reflect directional shifts in several mean community traits that underlie tree growth with decreases in site temperature. Main conclusions The observed shift in traits of trees that dominate in more cold environments is consistent with an ‘adaptive/acclimatory’ compensation for the kinetic effects of temperature on leaf photosynthesis and tree growth. Forest trait distributions across the gradient showed overly peaked and skewed distributions, consistent with the importance of local filtering of optimal growth traits and recent shifts in species composition and dominance attributable to warming from climate change. Trait‐based scaling theory provides a basis to predict how shifts in climate have and will influence the trait composition and ecosystem functioning of tropical forests.

Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish - Frederic Grandjean; Mun Hua Tan; Han Ming Gan; Yin Peng Lee; Tadashi Kawai; Robert J. Distefano; Martin Blaha; Angela J. Roles; Christopher M. Austin (Zoologica Scripta, 2017)
Molecular phylogenetics has benefited tremendously from the advent of next‐generation sequencing, enabling quick and cost‐effective recovery of whole mitogenomes via an approach referred to as ‘genome skimming’. Recently, genome skimming has been utilised to recover highly repetitive nuclear genes such as 18S and 28S ribosomal RNA genes that are useful for inferring deeper evolutionary relationships. To address some outstanding issues in the relationships among Northern Hemisphere freshwater crayfish (Astacoidea), we sequenced the partial genome of crayfish species from Asian, North American and European genera and report the successful recovery of whole mitogenome sequences in addition to three highly repetitive nuclear genes, namely histone H3, 18S and 28S ribosomal RNA . Consistent with some previous studies using short mt DNA and nuclear gene fragments, phylogenetic analyses based on the concatenation of recovered mitochondrial and/or nuclear sequences recovered the Asian cambarid lineage as basal to all astacids and North American cambarids, which conflicts with the current taxonomic classification based on morphological and reproduction‐related characters. Lastly, we show that complete H3, 18S and 28S ribosomal RNA genes can also be consistently recovered from a diverse range of animal taxa, demonstrating the potential wide utility of genome skimming for nuclear markers.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Abundant carbon substrates drive extremely high sulfate reduction rates and methane fluxes in Prairie Pothole Wetlands - Paula Dalcin Martins; David W. Hoyt; Sheel Bansal; Christopher T. Mills; Malak Tfaily; Brian A. Tangen; Raymond G. Finocchiaro; Michael D. Johnston; Brandon C. McAdams; Matthew J. Solensky; Garrett J. Smith; Yu‐Ping Chin; et al. (Global Change Biology, 2017)
Inland waters are increasingly recognized as critical sites of methane emissions to the atmosphere, but the biogeochemical reactions driving such fluxes are less well understood. The Prairie Pothole Region ( PPR ) of North America is one of the largest wetland complexes in the world, containing millions of small, shallow wetlands. The sediment pore waters of PPR wetlands contain some of the highest concentrations of dissolved organic carbon ( DOC ) and sulfur species ever recorded in terrestrial aquatic environments. Using a suite of geochemical and microbiological analyses, we measured the impact of sedimentary carbon and sulfur transformations in these wetlands on methane fluxes to the atmosphere. This research represents the first study of coupled geochemistry and microbiology within the PPR and demonstrates how the conversion of abundant labile DOC pools into methane results in some of the highest fluxes of this greenhouse gas to the atmosphere ever reported. Abundant DOC and sulfate additionally supported some of the highest sulfate reduction rates ever measured in terrestrial aquatic environments, which we infer to account for a large fraction of carbon mineralization in this system. Methane accumulations in zones of active sulfate reduction may be due to either the transport of free methane gas from deeper locations or the co‐occurrence of methanogenesis and sulfate reduction. If both respiratory processes are concurrent, any competitive inhibition of methanogenesis by sulfate‐reducing bacteria may be lessened by the presence of large labile DOC pools that yield noncompetitive substrates such as methanol. Our results reveal some of the underlying mechanisms that make PPR wetlands biogeochemical hotspots, which ultimately leads to their critical, but poorly recognized role in regional greenhouse gas emissions.

Similarity in volatile communities leads to increased herbivory and greater tropical forest diversity - Tara J. Massad; Marcílio Martins de Moraes; Casey Philbin; Celso Oliveira; Gerardo Cebrian Torrejon; Lydia Fumiko Yamaguchi; Christopher S. Jeffrey; Lee A. Dyer; Lora A. Richards; Massuo J. Kato (Ecology, 2017)
A longstanding paradigm in ecology is that there are positive associations between herbivore diversity, specialization, and plant species diversity, with a focus on taxonomic diversity. However, phytochemical diversity is also an informative metric, as insect herbivores interact with host plants not as taxonomic entities, but as sources of nutrients, primary metabolites, and mixtures of attractant and repellant chemicals. The present research examines herbivore responses to phytochemical diversity measured as volatile similarity in the tropical genus Piper . We quantified associations between naturally occurring volatile variation and herbivory by specialist and generalist insects. Intraspecific similarity of volatile compounds across individuals was associated with greater overall herbivory. A structural equation model supported the hypothesis that plot level volatile similarity caused greater herbivory by generalists, but not specialists, which led to increased understory plant richness. These results demonstrate that using volatiles as a functional diversity metric is informative for understanding tropical forest diversity and indicate that generalist herbivores contribute to the maintenance of diversity.

ECG imaging of ventricular tachycardia: evaluation against simultaneous non-contact mapping and CMR-derived grey zone - Walther H. W. Schulze; Zhong Chen; Jatin Relan; Danila Potyagaylo; Martin W. Krueger; Rashed Karim; Manav Sohal; Anoop Shetty; YingLiang Ma; Nicholas Ayache; Maxime Sermesant; Herve Delingette; et al. (Medical & Biological Engineering & Computing, 2017)

Biogeochemical controls on mercury methylation in the Allequash Creek wetland - Joel E. Creswell; Martin M. Shafer; Christopher L. Babiarz; Sue-Zanne Tan; Abbey L. Musinsky; Trevor H. Schott; Eric E. Roden; David E. Armstrong (Environmental Science and Pollution Research, 2017)

Warming of Central European lakes and their response to the 1980s climate regime shift - R. Iestyn Woolway; Martin T. Dokulil; Wlodzimierz Marszelewski; Martin Schmid; Damien Bouffard; Christopher J. Merchant (Climatic Change, 2017)

Natural resource landscapes of a marine bacterium reveal distinct fitness‐determining genes across the genome - Alison F. Takemura; Christopher H. Corzett; Fatima Hussain; Philip Arevalo; Manoshi Datta; Xiaoqian Yu; Frederique Le Roux; Martin F. Polz (Environmental Microbiology, 2017)
Summary Heterotrophic bacteria exploit diverse microhabitats in the ocean, from particles to transient gradients. Yet the degree to which genes and pathways can contribute to an organism's fitness on such complex and variable natural resource landscapes remains poorly understood. Here, we determine the gene‐by‐gene fitness of a generalist saprophytic marine bacterium ( Vibrio sp. F13 9CS106) on complex resources derived from its natural habitats – copepods ( Apocyclops royi ) and brown algae ( Fucus vesiculosus ) – and as reference substrates, glucose and the polysaccharide alginate, derived from brown algal cell walls. We find that resource complexity strongly buffers fitness costs of mutations, and that anabolic rather than catabolic pathways are more stringently required, likely due to functional redundancy in the latter. Moreover, while carbohydrate‐rich algae requires several synthesis pathways, protein‐rich Apocyclops does not, suggesting this ancestral habitat for Vibrios is a replete medium with metabolically redundant substrates. We also identify a candidate fitness trade‐off for algal colonization: deletion of mshA increases mutant fitness. Our results demonstrate that gene fitness depends on habitat composition, and suggest that this generalist uses distinct resources in different natural habitats. The results further indicate that substrate replete conditions may lead to relatively relaxed selection on catabolic genes.

Sexual dimorphism in obesity-related genes in the epicardial fat during aging - Caitlin Kocher; Matthew Christiansen; Sarah Martin; Christopher Adams; Paulette Wehner; Todd Gress; Nalini Santanam (Journal of Physiology and Biochemistry, 2017)

Aerosol emissions of a ship diesel engine operated with diesel fuel or heavy fuel oil - Thorsten Streibel; Jürgen Schnelle-Kreis; Hendryk Czech; Horst Harndorf; Gert Jakobi; Jorma Jokiniemi; Erwin Karg; Jutta Lintelmann; Georg Matuschek; Bernhard Michalke; Laarnie Müller; Jürgen Orasche; et al. (Environmental Science and Pollution Research, 2017)

In Silico and In Vivo Experiments Reveal M-CSF Injections Accelerate Regeneration Following Muscle Laceration - Kyle S. Martin; Christopher D. Kegelman; Kelley M. Virgilio; Julianna A. Passipieri; George J. Christ; Silvia S. Blemker; Shayn M. Peirce (Annals of Biomedical Engineering, 2017)

The rediscovery of Orthoceratium lacustre (Scopoli, 1763) (Diptera: Dolichopodidae) in Belgium, with data on its ecology and distribution in the Palaearctic region - Marc Pollet; Anja De Braekeleer; Christopher Martin Drake; Frank Van de Meutter (Biologia, 2017)

The genetic architecture of novel trophic specialists: larger effect sizes are associated with exceptional oral jaw diversification in a pupfish adaptive radiation - Christopher H. Martin; Priscilla A. Erickson; Craig T. Miller (Molecular Ecology, 2017)
The genetic architecture of adaptation is fundamental to understanding the mechanisms and constraints governing diversification. However, most case studies focus on loss of complex traits or parallel speciation in similar environments. It is still unclear how the genetic architecture of these local adaptive processes compares to the architecture of evolutionary transitions contributing to morphological and ecological novelty. Here, we identify quantitative trait loci ( QTL ) between two trophic specialists in an excellent case study for examining the origins of ecological novelty: a sympatric radiation of pupfishes endemic to San Salvador Island, Bahamas, containing a large‐jawed scale‐eater and a short‐jawed molluscivore with a skeletal nasal protrusion. These specialized niches and trophic traits are unique among over 2000 related species. Measurements of the fitness landscape on San Salvador demonstrate multiple fitness peaks and a larger fitness valley isolating the scale‐eater from the putative ancestral intermediate phenotype of the generalist, suggesting that more large‐effect QTL should contribute to its unique phenotype. We evaluated this prediction using an F2 intercross between these specialists. We present the first linkage map for pupfishes and detect significant QTL for sex and eight skeletal traits. Large‐effect QTL contributed more to enlarged scale‐eater jaws than the molluscivore nasal protrusion, consistent with predictions from the adaptive landscape. The microevolutionary genetic architecture of large‐effect QTL for oral jaws parallels the exceptional diversification rates of oral jaws within the San Salvador radiation observed over macroevolutionary timescales and may have facilitated exceptional trophic novelty in this system.

Genome‐wide association of functional traits linked with C ampylobacter jejuni survival from farm to fork - Koji Yahara; Guillaume Méric; Aidan J. Taylor; Stefan P. W. de Vries; Susan Murray; Ben Pascoe; Leonardos Mageiros; Alicia Torralbo; Ana Vidal; Anne Ridley; Sho Komukai; Helen Wimalarathna; et al. (Environmental Microbiology, 2017)
Summary Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.

Controls on the Geochemical Evolution of Prairie Pothole Region Lakes and Wetlands Over Decadal Time Scales - Martin B. Goldhaber; Christopher T. Mills; David M. Mushet; Blaine B. McCleskey; Jennifer Rover (Wetlands, 2016)

Changes in Pond Water Levels and Surface Extent Due to Climate Variability Alter Solute Sources to Closed-Basin Prairie-Pothole Wetland Ponds, 1979 to 2012 - James W. LaBaugh; David M. Mushet; Donald O. Rosenberry; Ned H. Euliss; Martin B. Goldhaber; Christopher T. Mills; Richard D. Nelson (Wetlands, 2016)

Differential vascular reactivity responses acutely following ingestion of a nitrate rich red spinach extract - Cody T. Haun; Wesley C. Kephart; Angelia M. Holland; Christopher B. Mobley; Anna E. McCloskey; Joshua J. Shake; David D. Pascoe; Michael D. Roberts; Jeffrey S. Martin (European Journal of Applied Physiology, 2016)

Distribution and expression of microbial rhodopsins in the Baltic Sea and adjacent waters - Björn Brindefalk; Martin Ekman; Karolina Ininbergs; Christopher L. Dupont; Shibu Yooseph; Jarone Pinhassi; Birgitta Bergman (Environmental Microbiology, 2016)
Summary Rhodopsins are light‐driven ion‐pumping membrane proteins found in many organisms and are proposed to be of global importance for oceanic microbial energy generation. Several studies have focused on marine environments, with less exploration of rhodopsins in brackish waters. We investigated microbial rhodopsins in the Baltic Sea using size‐fractionated metagenomic and metatranscriptomic datasets collected along a salinity gradient spanning from ∼0 to 35 PSU. The normalised genomic abundance of rhodopsins in Bacteria, as well as rhodopsin gene expression, was highest in the smallest size fraction (0.1–0.8 μ m), relative to the medium (0.8–3.0 μ m) and large (>3.0 μ m) size fractions. The abundance of rhodopsins in the two smaller size fractions displayed a positive correlation with salinity. Proteobacteria and Bacteroidetes rhodopsins were the most abundant while Actinobacteria rhodopsins, or actinorhodopsins, were common at lower salinities. Phylogenetic analysis indicated that rhodopsins have adapted independently to the marine‐brackish transition on multiple occasions, giving rise to green light‐adapted variants from ancestral blue light‐adapted ones. A notable diversity of viral‐like rhodopsins was also detected in the dataset and potentially linked with eukaryotic phytoplankton blooms. Finally, a new clade of likely proton‐pumping rhodopsin with non‐canonical amino acids in the spectral tuning and proton accepting site was identified.

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Physicochemical and Preclinical Evaluation of a Novel Buccal Measles Vaccine - Rikhav P. Gala; Carmen Popescu; Gregory T. Knipp; Robyn R. McCain; Ruhi V. Ubale; Richard Addo; Tuhin Bhowmik; Christopher D. Kulczar; Martin J. D’Souza (AAPS PharmSciTech, 2016)

Xenopus LAP2β protein knockdown affects location of lamin B and nucleoporins and has effect on assembly of cell nucleus and cell viability - Magda Dubińska-Magiera; Magdalena Chmielewska; Katarzyna Kozioł; Magdalena Machowska; Christopher J. Hutchison; Martin W. Goldberg; Ryszard Rzepecki (Protoplasma, 2016)
Xenopus LAP2β protein is the single isoform expressed in XTC cells. The protein localizes on heterochromatin clusters both at the nuclear envelope and inside a cell nucleus. The majority of XLAP2β fraction neither colocalizes with TPX2 protein during interphase nor can be immunoprecipitated with XLAP2β antibody. Knockdown of the XLAP2β protein expression in XTC cells by synthetic siRNA and plasmid encoded siRNA resulted in nuclear abnormalities including changes in shape of nuclei, abnormal chromatin structure, loss of nuclear envelope, mislocalization of integral membrane proteins of INM such as lamin B2, mislocalization of nucleoporins, and cell death. Based on timing of cell death, we suggest mechanism associated with nucleus reassembly or with entry into mitosis. This confirms that Xenopus LAP2 protein is essential for the maintenance of cell nucleus integrity and the process of its reassembly after mitosis.

A moving target—incorporating knowledge of the spatial ecology of fish into the assessment and management of freshwater fish populations - Steven J. Cooke; Eduardo G. Martins; Daniel P. Struthers; Lee F. G. Gutowsky; Michael Power; Susan E. Doka; John M. Dettmers; David A. Crook; Martyn C. Lucas; Christopher M. Holbrook; Charles C. Krueger (Environmental Monitoring and Assessment, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

The farmer as a landscape steward: Comparing local understandings of landscape stewardship, landscape values, and land management actions - Christopher M. Raymond; Claudia Bieling; Nora Fagerholm; Berta Martin-Lopez; Tobias Plieninger (Ambio, 2016)

Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Fatty Acid Binding Proteins Expressed at the Human Blood–Brain Barrier Bind Drugs in an Isoform-Specific Manner - Gordon S. Lee; Katharina Kappler; Christopher J. H. Porter; Martin J. Scanlon; Joseph A. Nicolazzo (Pharmaceutical Research, 2015)

The Carnian/Norian boundary succession at Berlin-Ichthyosaur State Park (Upper Triassic, central Nevada, USA) - Marco Balini; James F. Jenks; Riccardo Martin; Christopher A. McRoberts; Michael J. Orchard; Norman J. Silberling (PalZ, 2015)

Ecology, culture, and management of Burbot: an introduction - Martin A. Stapanian; Christopher A. Myrick (Hydrobiologia, 2015)

Bay breeze influence on surface ozone at Edgewood, MD during July 2011 - Ryan M. Stauffer; Anne M. Thompson; Douglas K. Martins; Richard D. Clark; Daniel L. Goldberg; Christopher P. Loughner; Ruben Delgado; Russell R. Dickerson; Jeffrey W. Stehr; Maria A. Tzortziou (Journal of Atmospheric Chemistry, 2015)

Unexpected warming‐induced growth decline in Thuja occidentalis at its northern limits in North America - Johann M. Housset; Martin P. Girardin; Mathieu Baconnet; Christopher Carcaillet; Yves Bergeron (Journal of Biogeography, 2015)
Aim Towards the cold margins of the Northern Hemisphere boreal zone, continuing warming should theoretically provide a longer vegetative season, favouring growth and a northward shift in tree species distribution. The northern distribution of Thuja occidentalis L. (eastern white cedar) is marked by the presence of isolated marginal populations distant from the continuous distribution. If those populations proved to be well adapted to their future local climatic conditions, their expansion could accelerate cedar poleward migration. We tested the hypotheses that (1) there will be a growth increase in cedar northern marginal populations as a result of global warming, and (2) the edaphic conditions and regional precipitation regimes will modulate their response to warming. Location Canadian boreal forest, western Québec (47–50° N, 74–80° W). Methods We investigated radial growth using tree‐ring measurements from dominant and co‐dominant eastern white cedar trees ( n = 723) distributed along a latitudinal gradient from the species' northern margin to the centre of its natural range. First, low‐frequency growth variations were analysed on whole chronologies ( ad 1720–2010). Second, inter‐annual growth variations were tested against ad 1953–2010 monthly temperature and precipitation time series with a bootstrapped correlation function. Finally, the impact of environmental variables on the growth–climate relationships was assessed. Results Unexpectedly, a growth decline was observed starting in 1980 in marginal sites. Dendroclimatic analyses revealed that radial growth was not only limited by short growing seasons but also by summer droughts in the marginal zone. This response was exacerbated in sites that received less summer precipitation. Counterintuitively, autumn and spring precipitation negatively impacted on growth, especially in wet soil stands. Main conclusions Northern marginal populations of cedar may have already reached their optimum temperature threshold for radial growth. Our results suggest that they will probably be facing increasing hydric stress selection pressure under the assumptions of climate change. Their responses to future warming will be highly dependent on the seasonality and magnitude of variation in precipitation regimes.

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Modifiers of (CAG)n instability in Machado–Joseph disease (MJD/SCA3) transmissions: an association study with DNA replication, repair and recombination genes - Sandra Martins; Christopher E. Pearson; Paula Coutinho; Sylvie Provost; António Amorim; Marie-Pierre Dubé; Jorge Sequeiros; Guy A. Rouleau (Human Genetics, 2014)

An Internet survey of marijuana and hot shower use in adults with cyclic vomiting syndrome (CVS) - Thangam Venkatesan; Jyotirmoy Sengupta; Atena Lodhi; Abigail Schroeder; Kathleen Adams; Walter J. Hogan; Yanzhi Wang; Christopher Andrews; Martin Storr (Experimental Brain Research, 2014)

An Experimental Study of Three-Phase Trapping in Sand Packs - Benny Amaechi; Stefan Iglauer; Christopher H. Pentland; Branko Bijeljic; Martin J. Blunt (Transport in Porous Media, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The longitudinal and interactive effects of HIV status, stimulant use, and host genotype upon neurocognitive functioning - Andrew J. Levine; Sandra Reynolds; Christopher Cox; Eric N. Miller; Janet S. Sinsheimer; James T. Becker; Eileen Martin; Ned Sacktor (Journal of NeuroVirology, 2014)

Regional brain distribution of translocator protein using [11C]DPA-713 PET in individuals infected with HIV - Jennifer M. Coughlin; Yuchuan Wang; Shuangchao Ma; Chen Yue; Pearl K. Kim; Ashley V. Adams; Heidi V. Roosa; Kenneth L. Gage; Marigo Stathis; Rana Rais; Camilo Rojas; Jennifer L. McGlothan; et al. (Journal of NeuroVirology, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Novel trophic niches drive variable progress towards ecological speciation within an adaptive radiation of pupfishes - Christopher H. Martin; Laura C. Feinstein (Molecular Ecology, 2014)
Adaptive radiation is recognized by a rapid burst of phenotypic, ecological and species diversification. However, it is unknown whether different species within an adaptive radiation evolve reproductive isolation at different rates. We compared patterns of genetic differentiation between nascent species within an adaptive radiation of Cyprinodon pupfishes using genotyping by sequencing. Similar to classic adaptive radiations, this clade exhibits rapid morphological diversification rates and two species are novel trophic specialists, a scale‐eater and hard‐shelled prey specialist (durophage), yet the radiation is SNP s), we found consistent differences in genetic differentiation between each specialist species and the generalist across seven lakes. The scale‐eater showed the greatest genetic differentiation and clustered by species across lakes, whereas durophage populations often clustered with sympatric generalist populations, consistent with parallel speciation across lakes. However, we found strong evidence of admixture between durophage populations in different lakes, supporting a single origin of this species and genome‐wide introgression with sympatric generalist populations. We conclude that the scale‐eater is further along the speciation‐with‐gene‐flow continuum than the durophage and suggest that different adaptive landscapes underlying these two niche environments drive variable progress towards speciation within the same habitat. Our previous measurements of fitness surfaces in these lakes support this conclusion: the scale‐eating fitness peak may be more distant than the durophage peak on the complex adaptive landscape driving adaptive radiation.

Response of Lake Pontchartrain Fish Assemblages to Hurricanes Katrina and Rita - Martin T. O’Connell; Ann M. U. O’Connell; Christopher S. Schieble (Estuaries and Coasts, 2014)

Herbivory makes major contributions to ecosystem carbon and nutrient cycling in tropical forests - Daniel B. Metcalfe; Gregory P. Asner; Roberta E. Martin; Javier E. Silva Espejo; Walter Huaraca Huasco; Felix F. Farfán Amézquita; Loreli Carranza‐Jimenez; Darcy F. Galiano Cabrera; Liliana Durand Baca; Felipe Sinca; Lidia P. Huaraca Quispe; Ivonne Alzamora Taype; et al. (Ecology Letters, 2014)
The functional role of herbivores in tropical rainforests remains poorly understood. We quantified the magnitude of, and underlying controls on, carbon, nitrogen and phosphorus cycled by invertebrate herbivory along a 2800 m elevational gradient in the tropical Andes spanning 12°C mean annual temperature. We find, firstly, that leaf area loss is greater at warmer sites with lower foliar phosphorus, and secondly, that the estimated herbivore‐mediated flux of foliar nitrogen and phosphorus from plants to soil via leaf area loss is similar to, or greater than, other major sources of these nutrients in tropical forests. Finally, we estimate that herbivores consume a significant portion of plant carbon, potentially causing major shifts in the pattern of plant and soil carbon cycling. We conclude that future shifts in herbivore abundance and activity as a result of environmental change could have major impacts on soil fertility and ecosystem carbon sequestration in tropical forests.

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

On the relationship between vegetation and climate in tropical and northern Africa - Martin Schmidt; Doris Klein; Christopher Conrad; Stefan Dech; Heiko Paeth (Theoretical and Applied Climatology, 2014)

Modelling macronutrients in shelf sea sediments: fitting model output to experimental data using a genetic algorithm - Christopher C. Wood; Peter J. Statham; Boris A. Kelly-Gerreyn; Adrian P. Martin (Journal of Soils and Sediments, 2014)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Gastric cancer incidence estimation in a resource-limited nation: use of endoscopy registry methodology - Ricardo L. Dominguez; Seth D. Crockett; Jennifer L. Lund; Lia P. Suazo; Paris Heidt; Christopher Martin; Douglas R. Morgan (Cancer Causes & Control, 2013)

Neuropsychological test performance before and after HIV-1 seroconversion: the Multicenter AIDS Cohort Study - Quynh T. Vo; Christopher Cox; Xiuhong Li; Lisa P. Jacobson; Rosemary McKaig; Ned Sacktor; Ola A. Selnes; Eileen Martin; James T. Becker; Eric N. Miller (Journal of NeuroVirology, 2013)

A plant's perspective of extremes: terrestrial plant responses to changing climatic variability - Christopher P.O. Reyer; Sebastian Leuzinger; Anja Rammig; Annett Wolf; Ruud P. Bartholomeus; Antonello Bonfante; Francesca de Lorenzi; Marie Dury; Philipp Gloning; Renée Abou Jaoudé; Tamir Klein; Thomas M. Kuster; et al. (Global Change Biology, 2013)
We review observational, experimental, and model results on how plants respond to extreme climatic conditions induced by changing climatic variability. Distinguishing between impacts of changing mean climatic conditions and changing climatic variability on terrestrial ecosystems is generally underrated in current studies. The goals of our review are thus (1) to identify plant processes that are vulnerable to changes in the variability of climatic variables rather than to changes in their mean, and (2) to depict/evaluate available study designs to quantify responses of plants to changing climatic variability. We find that phenology is largely affected by changing mean climate but also that impacts of climatic variability are much less studied, although potentially damaging. We note that plant water relations seem to be very vulnerable to extremes driven by changes in temperature and precipitation and that heatwaves and flooding have stronger impacts on physiological processes than changing mean climate. Moreover, interacting phenological and physiological processes are likely to further complicate plant responses to changing climatic variability. Phenological and physiological processes and their interactions culminate in even more sophisticated responses to changing mean climate and climatic variability at the species and community level. Generally, observational studies are well suited to study plant responses to changing mean climate, but less suitable to gain a mechanistic understanding of plant responses to climatic variability. Experiments seem best suited to simulate extreme events. In models, temporal resolution and model structure are crucial to capture plant responses to changing climatic variability. We highlight that a combination of experimental, observational, and/or modeling studies have the potential to overcome important caveats of the respective individual approaches.

Climate change adaptation and sustainable regional development: a case study for the Federal State of Brandenburg, Germany - Christopher Reyer; Johann Bachinger; Ralf Bloch; Fred F. Hattermann; Pierre L. Ibisch; Stefan Kreft; Petra Lasch; Wolfgang Lucht; Christoph Nowicki; Peter Spathelf; Manfred Stock; Martin Welp (Regional Environmental Change, 2012)

Validation of a reduced combustion mechanism for light hydrocarbons - Helen H. Lou; Daniel Chen; Christopher B. Martin; Xianchang Li; Kyuen Li; Hitesh Vaid; Anjan Tula Kumar; Kanwar Devesh Singh (Clean Technologies and Environmental Policy, 2012)

Ferumoxytol-Enhanced MRI to Image Inflammation Within Human Brain Arteriovenous Malformations: a Pilot Investigation - David M. Hasan; Matthew Amans; Tarik Tihan; Christopher Hess; Yi Guo; Soonmee Cha; Hua Su; Alastair J. Martin; Michael T. Lawton; Edward A. Neuwelt; David A. Saloner; William L. Young (Translational Stroke Research, 2012)

The immunopathogenesis of celiac disease reveals possible therapies beyond the gluten-free diet - Christopher S. McAllister; Martin F. Kagnoff (Seminars in Immunopathology, 2012)

Climate change and future temperature-related mortality in 15 Canadian cities - Sara Lauretta Martin; Sabit Cakmak; Christopher Alan Hebbern; Mary-Luyza Avramescu; Neil Tremblay (International Journal of Biometeorology, 2012)

Anwendungsbeispiele für die Verwendung neuer analytischer Prüftechniken bei Hochleistungsstählen - Ralph Werl; Gerald Klösch; Waltraud Winkler; Andreas Pissenberger; Martin W. Egger; Stefan Aigner; Jürgen Pühringer; Susanne Michelic; Christian Bernhard; Wolfgang Schützenhöfer; Reinhold Schneider; Christopher Schüller (BHM Berg- und Hüttenmännische Monatshefte, 2012)

QTL linkage analysis of connected populations using ancestral marker and pedigree information - Marco C. A. M. Bink; L. Radu Totir; Cajo J. F. ter Braak; Christopher R. Winkler; Martin P. Boer; Oscar S. Smith (Theoretical and Applied Genetics, 2012)

A reduced reaction mechanism for the simulation in ethylene flare combustion - Helen H. Lou; Christopher B. Martin; Daniel Chen; Xianchang Li; Kyuen Li; Hitesh Vaid; Anjan Tula Kumar; Kanwar Devesh Singh; Doyle P. Bean (Clean Technologies and Environmental Policy, 2012)

Erratum to:Dengue virus-specific CD4+ and CD8+ T lymphocytes target NS1, NS3 and NS5 in infected Indian rhesus macaques - Katherine M. Mladinich; Shari M. Piaskowski; Richard Rudersdorf; Christopher M. Eernisse; Kim L. Weisgrau; Mauricio A. Martins; Jessica R. Furlott; Charalambos D. Partidos; Joseph N. Brewoo; Jorge E. Osorio; Nancy A. Wilson; Eva G. Rakasz; et al. (Immunogenetics, 2012)

Muscle-Specific RING Finger (MuRF) cDNAs in Atlantic Salmon (Salmo salar) and Their Role as Regulators of Muscle Protein Degradation - Luca Tacchi; Ralph Bickerdike; Christopher J. Secombes; Samuel A. M. Martin (Marine Biotechnology, 2012)

Dengue virus-specific CD4+ and CD8+ T lymphocytes target NS1, NS3 and NS5 in infected Indian rhesus macaques - Katherine M. Mladinich; Shari M. Piaskowski; Richard Rudersdorf; Christopher M. Eernisse; Kim L. Weisgrau; Mauricio A. Martins; Jessica R. Furlott; Charalambos D. Partidos; Joseph N. Brewoo; Jorge E. Osorio; Nancy A. Wilson; Eva G. Rakasz; et al. (Immunogenetics, 2012)

Extensive gene flow over Europe and possible speciation over Eurasia in the ectomycorrhizal basidiomycete Laccaria amethystina complex - LUCIE VINCENOT; KAZUHIDE NARA; CHRISTOPHER STHULTZ; JESSY LABBÉ; MARIE‐PIERRE DUBOIS; LEHO TEDERSOO; FRANCIS MARTIN; MARC‐ANDRÉ SELOSSE (Molecular Ecology, 2012)
Biogeographical patterns and large‐scale genetic structure have been little studied in ectomycorrhizal (EM) fungi, despite the ecological and economic importance of EM symbioses. We coupled population genetics and phylogenetic approaches to understand spatial structure in fungal populations on a continental scale. Using nine microsatellite markers, we characterized gene flow among 16 populations of the widespread EM basidiomycete Laccaria amethystina over Europe (i.e. over 2900 km). We also widened our scope to two additional populations from Japan (10 4 km away) and compared them with European populations through microsatellite markers and multilocus phylogenies, using three nuclear genes ( NAR , G6PD and ribosomal DNA) and two mitochondrial ribosomal genes. European L. amethystina populations displayed limited differentiation (average F ST = 0.041) and very weak isolation by distance (IBD). This panmictic European pattern may result from effective aerial dispersal of spores, high genetic diversity in populations and mutualistic interactions with multiple hosts that all facilitate migration. The multilocus phylogeny based on nuclear genes confirmed that Japanese and European specimens were closely related but clustered on a geographical basis. By using microsatellite markers, we found that Japanese populations were strongly differentiated from the European populations ( F ST = 0.416), more than expected by extrapolating the European pattern of IBD. Population structure analyses clearly separated the populations into two clusters, i.e. European and Japanese clusters. We discuss the possibility of IBD in a continuous population (considering some evidence for a ring species over the Northern Hemisphere) vs. an allopatric speciation over Eurasia, making L. amethystina a promising model of intercontinental species for future studies.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Efficient electron transfer from hydrogen to benzyl viologen by the [NiFe]-hydrogenases of Escherichia coli is dependent on the coexpression of the iron–sulfur cluster-containing small subunit - Constanze Pinske; Sara Krüger; Basem Soboh; Christian Ihling; Martin Kuhns; Mario Braussemann; Monique Jaroschinsky; Christopher Sauer; Frank Sargent; Andrea Sinz; R. Gary Sawers (Archives of Microbiology, 2011)

The Multiple Faces of Valosin-Containing Protein-Associated Diseases: Inclusion Body Myopathy with Paget’s Disease of Bone, Frontotemporal Dementia, and Amyotrophic Lateral Sclerosis - Angèle Nalbandian; Sandra Donkervoort; Eric Dec; Mallikarjun Badadani; Veeral Katheria; Prachi Rana; Christopher Nguyen; Jogeshwar Mukherjee; Vincent Caiozzo; Barbara Martin; Giles D. Watts; Jouni Vesa; et al. (Journal of Molecular Neuroscience, 2011)

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Refractory dispersion promotes conduction disturbance and arrhythmias in a Scn5a +/− mouse model - Claire A. Martin; Andrew A. Grace; Christopher L.-H. Huang (Pflügers Archiv - European Journal of Physiology, 2011)

Automated multidimensional single molecule fluorescence microscopy feature detection and tracking - Daniel J. Rolfe; Charles I. McLachlan; Michael Hirsch; Sarah R. Needham; Christopher J. Tynan; Stephen E. D. Webb; Marisa L. Martin-Fernandez; Michael P. Hobson (European Biophysics Journal, 2011)

Life history and habitat use of the speckled worm eel, Myrophis punctatus, along the east coast of the United States - Kenneth W. Able; Dennis M. Allen; Gretchen Bath-Martin; Jonathan A. Hare; Donald E. Hoss; Katrin E. Marancik; Perce M. Powles; David E. Richardson; J. Christopher Taylor; Harvey J. Walsh; Stanley M. Warlen; Charles Wenner (Environmental Biology of Fishes, 2011)

Fatty Acid Binding Proteins: Potential Chaperones of Cytosolic Drug Transport in the Enterocyte? - Natalie L. Trevaskis; Gary Nguyen; Martin J. Scanlon; Christopher J. H. Porter (Pharmaceutical Research, 2011)

A Synthesis of the Long-Term Paleoclimatic Evolution of the Arctic - Matthew O'Regan; Christopher Williams; Karen Frey; Martin Jakobsson (Oceanography, 2011)

The Neural Substrate of Predictive Motor Timing in Spinocerebellar Ataxia - Martin Bares; Ovidiu V. Lungu; Tao Liu; Tobias Waechter; Christopher M. Gomez; James Ashe (The Cerebellum, 2011)

The contribution of haemoglobin mass to increases in cycling performance induced by simulated LHTL - Laura A. Garvican; Torben Pottgiesser; David T. Martin; Yorck Olaf Schumacher; Martin Barras; Christopher J. Gore (European Journal of Applied Physiology, 2011)

Quantitative trait loci analysis for resistance to Cephalosporium stripe, a vascular wilt disease of wheat - Martin C. Quincke; C. James Peterson; Robert S. Zemetra; Jennifer L. Hansen; Jianli Chen; Oscar Riera-Lizarazu; Christopher C. Mundt (Theoretical and Applied Genetics, 2011)

Two copies of the genes encoding the subunits of putative interleukin (IL)-4/IL-13 receptors, IL-4Rα, IL-13Rα1 and IL-13Rα2, have been identified in rainbow trout (Oncorhynchus mykiss) and have complex patterns of expression and modulation - Tiehui Wang; Wenshu Huang; Maria M. Costa; Samuel A. M. Martin; Christopher J. Secombes (Immunogenetics, 2011)

Embryonic and adult isoforms of XLAP2 form microdomains associated with chromatin and the nuclear envelope - Magdalena Chmielewska; Magda Dubińska-Magiera; Mirosław Sopel; Dorota Rzepecka; Christopher J. Hutchison; Martin W. Goldberg; Ryszard Rzepecki (Cell and Tissue Research, 2011)

Predicting tropical plant physiology from leaf and canopy spectroscopy - Christopher E. Doughty; Gregory P. Asner; Roberta E. Martin (Oecologia, 2011)

Bacterial ferrochelatase turns human: Tyr13 determines the apparent metal specificity of Bacillus subtilis ferrochelatase - Mattias D. Hansson; Tobias Karlberg; Christopher A. G. Söderberg; Sreekanth Rajan; Martin J. Warren; Salam Al-Karadaghi; Stephen E. J. Rigby; Mats Hansson (JBIC Journal of Biological Inorganic Chemistry, 2011)

Design, Optimization and Characterisation of Polymeric Microneedle Arrays Prepared by a Novel Laser-Based Micromoulding Technique - Ryan F. Donnelly; Rita Majithiya; Thakur Raghu Raj Singh; Desmond I. J. Morrow; Martin J. Garland; Yusuf K. Demir; Katarzyna Migalska; Elizabeth Ryan; David Gillen; Christopher J. Scott; A. David Woolfson (Pharmaceutical Research, 2011)

Longitudinal psychomotor speed performance in human immunodeficiency virus–seropositive individuals: impact of age and serostatus - Ned Sacktor; Richard L Skolasky; Christopher Cox; Ola Selnes; James T Becker; Bruce Cohen; Eileen Martin; Eric N Miller (Journal of NeuroVirology, 2010)

Modeling decay rates of dead wood in a neotropical forest - Bruno Hérault; Jacques Beauchêne; Félix Muller; Fabien Wagner; Christopher Baraloto; Lilian Blanc; Jean-Michel Martin (Oecologia, 2010)

Early adaptive developments of Pseudomonas aeruginosa after the transition from life in the environment to persistent colonization in the airways of human cystic fibrosis hosts - Martin Holm Rau; Susse Kirkelund Hansen; Helle Krogh Johansen; Line Elnif Thomsen; Christopher T. Workman; Kristian Fog Nielsen; Lars Jelsbak; Niels Høiby; Lei Yang; Søren Molin (Environmental Microbiology, 2010)
Summary Pseudomonas aeruginosa is an opportunistic pathogen ubiquitous to the natural environment but with the capability of moving to the host environment. Long‐term infection of the airways of cystic fibrosis patients is associated with extensive genetic adaptation of P. aeruginosa , and we have studied cases of the initial stages of infection in order to characterize the early adaptive processes in the colonizing bacteria. A combination of global gene expression analysis and phenotypic characterization of longitudinal isolates from cystic fibrosis patients revealed well‐known characteristics such as conversion to a mucoid phenotype by mucA mutation and increased antibiotic resistance by nfxB mutation. Additionally, upregulation of the atu operon leading to enhanced growth on leucine provides a possible example of metabolic optimization. A detailed investigation of the mucoid phenotype uncovered profound pleiotropic effects on gene expression including reduction of virulence factors and the Rhl quorum sensing system. Accordingly, mucoid isolates displayed a general reduction of virulence in the Caenorhabditis elegans infection model, altogether suggesting that the adaptive success of the mucoid variant extends beyond the benefits of alginate overproduction. In the overall perspective the global phenotype of the adapted variants appears to place them on paths in direction of fully adapted strains residing in long‐term chronically infected patients.

Seasonal variation of haemoglobin mass in internationally competitive female road cyclists - Laura A. Garvican; David T. Martin; Warren McDonald; Christopher J. Gore (European Journal of Applied Physiology, 2010)

Mixed model approaches for the identification of QTLs within a maize hybrid breeding program - Fred A. van Eeuwijk; Martin Boer; L. Radu Totir; Marco Bink; Deanne Wright; Christopher R. Winkler; Dean Podlich; Keith Boldman; Andy Baumgarten; Matt Smalley; Martin Arbelbide; Cajo J. F. ter Braak; et al. (Theoretical and Applied Genetics, 2010)

trans-Fatty acid consumption and its association with distal colorectal cancer in the North Carolina Colon Cancer Study II - Lisa C. Vinikoor; Robert C. Millikan; Jessie A. Satia; Jane C. Schroeder; Christopher F. Martin; Joseph G. Ibrahim; Robert S. Sandler (Cancer Causes & Control, 2010)

From Manganism to Manganese-Induced Parkinsonism: A Conceptual Model Based on the Evolution of Exposure - Roberto G. Lucchini; Christopher J. Martin; Brent C. Doney (NeuroMolecular Medicine, 2009)

Asenapine effects in animal models of psychosis and cognitive function - Hugh M. Marston; Jared W. Young; Frederic D. C. Martin; Kevin A. Serpa; Christopher L. Moore; Erik H. F. Wong; Lisa Gold; Leonard T. Meltzer; Marc R. Azar; Mark A. Geyer; Mohammed Shahid (Psychopharmacology, 2009)

Fluid-assisted zircon and monazite growth within a shear zone: a case study from Finnmark, Arctic Norway - Christopher L. Kirkland; Martin J. Whitehouse; Trond Slagstad (Contributions to Mineralogy and Petrology, 2009)

Heterogeneous response of circumboreal wildfire risk to climate change since the early 1900s - MARTIN P. GIRARDIN; ADAM A. ALI; CHRISTOPHER CARCAILLET; MANFRED MUDELSEE; IGOR DROBYSHEV; CHRISTELLE HÉLY; YVES BERGERON (Global Change Biology, 2009)
We investigated changes in wildfire risk over the 1901−2002 ( ad ) period with an analysis of broad‐scale patterns of July monthly drought code (MDC) variability on 28 forested ecoregions of the North American and Eurasian continents. The MDC is an estimate of the net effect of changes in evapotranspiration and precipitation on cumulative moisture depletion in soils, and is well correlated with annual fire statistics across the circumboreal (explaining 25–61% of the variance in regional area burned). We used linear trend and regime shift analyses to investigate (multi‐) decadal changes in MDC and percentage area affected by drought, and kernel function for analysis of temporal changes in the occurrence rates of extreme drought years. Our analyses did not reveal widespread patterns of linear increases in dryness through time as a response to rising Northern Hemisphere land temperatures. Instead, we found heterogeneous patterns of drought severity changes that were inherent to the nonuniformly distributed impacts of climate change on dryness. Notably, significant trends toward increasing summer moisture in southeastern and southwestern boreal Canada were detected. The diminishing wildfire risk in these regions is coherent with widely reported decreases in area burned since about 1850, as reconstructed by dendrochronological dating of forest stands. Conversely, we found evidence for increasing percentage area affected by extreme droughts in Eurasia (+0.57% per decade; P P =0.07). Although not statistically significant, temporal changes in occurrence rates are sufficiently important spatially to be paid further attention. The absence of a linear trend in MDC severity, in conjunction with the presence of an increase in the occurrence rate of extreme drought years, suggest that fire disturbance regimes in the Eurasian taiga could be shifting toward being increasingly pulse dependent.

Climate change mitigation via afforestation, reforestation and deforestation avoidance: and what about adaptation to environmental change? - Christopher Reyer; Martin Guericke; Pierre L. Ibisch (New Forests, 2009)

The Upper Cretaceous belemnite Praeactinocamax plenus (Blainville, 1827) from Lower Saxony (Upper Cenomanian, northwest Germany) and its distribution pattern in Europe - Frank Wiese; Martin Košták; Christopher J. Wood (PalZ, 2009)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Investigations into the Formulation of Metered Dose Inhalers of Salmeterol Xinafoate and Fluticasone Propionate Microcrystals - Darragh Murnane; Gary P. Martin; Christopher Marriott (Pharmaceutical Research, 2008)

Gold nanoparticles decorated with oligo(ethylene glycol) thiols: kinetics of colloid aggregation driven by depletion forces - Fajun Zhang; Donald G. Dressen; Maximilian W. A. Skoda; Robert M. J. Jacobs; Stefan Zorn; Richard A. Martin; Christopher M. Martin; Graham F. Clark; Frank Schreiber (European Biophysics Journal, 2008)

Detrimental effects of recent ocean surface warming on growth condition of Atlantic salmon - CHRISTOPHER D. TODD; SARAH L. HUGHES; C. TARA MARSHALL; JULIAN C. MacLEAN; MICHAEL E. LONERGAN; E. MARTIN BIUW (Global Change Biology, 2008)
Ocean climate impacts on survivorship and growth of Atlantic salmon are complex, but still poorly understood. Stock abundances have declined over the past three decades and 1992–2006 has seen widespread sea surface temperature (SST) warming of the NE Atlantic, including the foraging areas exploited by salmon of southern European origin. Salmon cease feeding on return migration, and here we express the final growth condition of year‐classes of one‐sea winter adults at, or just before, freshwater re‐entry as the predicted weight at standard length. Two independent 14‐year time series for a single river stock and for mixed, multiple stocks revealed almost identical temporal patterns in growth condition variation, and an overall trend decrease of 11–14% over the past decade. Growth condition has fallen as SST anomaly has risen, and for each year‐class the midwinter (January) SST anomalies they experienced at sea correlated negatively with their final condition on migratory return during the subsequent summer months. Stored lipids are crucial for survival and for the prespawning provisioning of eggs in freshwater, and we show that under‐weight individuals have disproportionately low reserves. The poorest condition fish (∼30% under‐weight) returned with lipid stores reduced by ∼80%. This study concurs with previous analyses of other North Atlantic top consumers (e.g. somatic condition of tuna, reproductive failure of seabirds) showing evidence of major, recent climate‐driven changes in the eastern North Atlantic pelagic ecosystem, and the likely importance of bottom‐up control processes. Because salmon abundances presently remain at historical lows, fecundity of recent year‐classes will have been increasingly compromised. Measures of year‐class growth condition should therefore be incorporated in the analysis and setting of numerical spawning escapements for threatened stocks, and conservation limits should be revised upwards conservatively during periods of excessive ocean climate warming.

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Aureoles of Pb(II)-enriched feldspar around monazite in paragneiss and anatectic pods of the Napier Complex, Enderby Land, East Antarctica: the roles of dissolution-reprecipitation and diffusion - Edward S. Grew; Martin G. Yates; Christopher J. L. Wilson (Contributions to Mineralogy and Petrology, 2008)

Episodic high intensity mixing events in a subterranean estuary: Effects of tropical cyclones - Christopher G. Smith; Jaye E. Cable; Jonathan B .Martin (Limnology and Oceanography, 2008)
Hydrostatic balances between fresh and saline groundwater and saline surface water control the physical and chemical framework of subterranean estuaries, but they are responsive to high frequency (waves and tides), low frequency (seasonal recharge patterns), and episodic (storm) events. In this study, we document a salinity and pressure perturbation to the subterranean estuary in east‐central Florida during and after the passage of Tropical Storm Tammy on 04 Oct 2005–05 Oct 2005 and Hurricane Wilma on 24 Oct 2005. These storms reversed hydraulic gradients, forced lagoon water into the aquifer, and shifted the outflow face landward. Salinity at 1.5 m and 2.5 m below a common datum converged on similar values intermediate between fresh and lagoon water salinities. The outflow face reestablished pre‐storm conditions after 80 days at 15 m offshore, but more than 160 days at 30 m offshore, confirming that both the flow field and fluid sources control the position of the subterranean estuary. Episodic, high intensity events could influence the biogeochemical setting of the subterranean estuary and the overlying water body by altering redox conditions in the subterranean estuary during the landward migration of the dispersive mixing zone, increasing short‐term discharge of potentially contaminated groundwater, and/or changing pore fluid residence time within the seepage face and along the mixing zone‐seepage face front.

Cultivation of a thermophilic ammonia oxidizing archaeon synthesizing crenarchaeol - José R. De La Torre; Christopher B. Walker; Anitra E. Ingalls; Martin Könneke; David A. Stahl (Environmental Microbiology, 2008)
Summary The widespread occurrence and diversity of ammonia oxidizing Archaea suggests their contribution to the nitrogen cycle is of global significance. Their distribution appeared limited to low‐ and moderate‐temperature environments until the recent finding of a diagnostic membrane lipid, crenarchaeol, in terrestrial hot springs. We report here the cultivation of a thermophilic nitrifier (‘ Candidatus Nitrosocaldus yellowstonii’), an autotrophic crenarchaeote growing up to 74°C by aerobic ammonia oxidation. The major core lipid of this archaeon growing at 72°C is crenarchaeol, providing the first direct evidence for its synthesis by a thermophile. These findings greatly extend the upper temperature limit of nitrification and document that the capacity for ammonia oxidation is broadly distributed among the Crenarchaeota .

Temperature and vegetation effects on soil organic carbon quality along a forested mean annual temperature gradient in North America - CINZIA FISSORE; CHRISTIAN P. GIARDINA; RANDALL K. KOLKA; CARL C. TRETTIN; GARY M. KING; MARTIN F. JURGENSEN; CHRISTOPHER D. BARTON; S. DOUGLAS MCDOWELL (Global Change Biology, 2008)
Both climate and plant species are hypothesized to influence soil organic carbon (SOC) quality, but accurate prediction of how SOC process rates respond to global change will require an improved understanding of how SOC quality varies with mean annual temperature (MAT) and forest type. We investigated SOC quality in paired hardwood and pine stands growing in coarse textured soils located along a 22 °C gradient in MAT. To do this, we conducted 80‐day incubation experiments at 10 and 30 °C to quantify SOC decomposition rates, which we used to kinetically define SOC quality. We used these experiments to test the hypotheses that SOC quality decreases with MAT, and that SOC quality is higher under pine than hardwood tree species. We found that both SOC quantity and quality decreased with increasing MAT. During the 30 °C incubation, temperature sensitivity ( Q 10 ) values were strongly and positively related to SOC decomposition rates, indicating that substrate supply can influence temperature responsiveness of SOC decomposition rates. For a limited number of dates, Q 10 was negatively related to MAT. Soil chemical properties could not explain observed patterns in soil quality. Soil pH and cation exchange capacity (CEC) both declined with increasing MAT, and soil C quality was positively related to pH but negatively related to CEC. Clay mineralogy of soils also could not explain patterns of SOC quality as complex (2 : 1), high CEC clay minerals occurred in cold climate soils while warm climate soils were dominated by simpler (1 : 1), low CEC clay minerals. While hardwood sites contained more SOC than pine sites, with differences declining with MAT, clay content was also higher in hardwood soils. In contrast, there was no difference in SOC quality between pine and hardwood soils. Overall, these findings indicate that SOC quantity and quality may both decrease in response to global warming, despite long‐term changes in soil chemistry and mineralogy that favor decomposition.

A field test of the Hamilton–Zuk hypothesis in the Trinidadian guppy (Poecilia reticulata) - Christopher H. Martin; Sönke Johnsen (Behavioral Ecology and Sociobiology, 2007)

Impaired predictive motor timing in patients with cerebellar disorders - Martin Bares; Ovidiu Lungu; Tao Liu; Tobias Waechter; Christopher M. Gomez; James Ashe (Experimental Brain Research, 2007)

Future extreme events in European climate: an exploration of regional climate model projections - Martin Beniston; David B. Stephenson; Ole B. Christensen; Christopher A. T. Ferro; Christoph Frei; Stéphane Goyette; Kirsten Halsnaes; Tom Holt; Kirsti Jylhä; Brigitte Koffi; Jean Palutikof; Regina Schöll; et al. (Climatic Change, 2007)

The locus encoding an oligomorphic family of MHC-A alleles (Mane-A*06/Mamu-A*05) is present at high frequency in several macaque species - Bernard A. P. Lafont; Christopher M. McGraw; Sabriya A. Stukes; Alicia Buckler-White; Ronald J. Plishka; Russell A. Byrum; Vanessa M. Hirsch; Malcolm A. Martin (Immunogenetics, 2007)

Parent satisfaction in a multi-site acute trial of risperidone in children with autism: a social validity study - Elaine Tierney; Michael Aman; David Stout; Krista Pappas; L. Eugene Arnold; Benedetto Vitiello; Lawrence Scahill; Christopher McDougle; James McCracken; Courtney Wheeler; Andres Martin; David Posey; et al. (Psychopharmacology, 2007)

Influence of Realistic Inspiratory Flow Profiles on Fine Particle Fractions of Dry Powder Aerosol Formulations - Gary P. Martin; Christopher Marriott; Xian-Ming Zeng (Pharmaceutical Research, 2007)

Variation of the Schmelzmuster and Other Enamel Characters in Molars of the Primitive Pliocene Vole Ogmodontomys from Kansas - Robert A. Martin; Christopher P. Crockett; Federica Marcolini (Journal of Mammalian Evolution, 2006)

Efficacy and Mechanisms of α-Solasonine-and α-Solamargine-Induced Cytolysis on Two Strains of Trypanosoma cruzi - Christopher A. Hall; Traci Hobby; Martin Cipollini (Journal of Chemical Ecology, 2006)

Potential of nine multipurpose tree species to reduce saline groundwater tables in the lower Amu Darya River region of Uzbekistan - Asia Khamzina; John P. A. Lamers; Christopher Martius; Martin Worbes; Paul L. G. Vlek (Agroforestry Systems, 2006)

Characterisation of a Carrier-Free Dry Powder Aerosol Formulation Using Inertial Impaction and Laser Diffraction - Gary P. Martin; Helen B. MacRitchie; Christopher Marriott; Xian-Ming Zeng (Pharmaceutical Research, 2006)

Correlation between Inertial Impaction and Laser Diffraction Sizing Data for Aerosolized Carrier-based Dry Powder Formulations - Xian-Ming Zeng; Helen B. MacRitchie; Christopher Marriott; Gary P. Martin (Pharmaceutical Research, 2006)

The Absorption of Darbepoetin Alfa Occurs Predominantly via the Lymphatics Following Subcutaneous Administration to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Anne C. Heatherington; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2006)

Variability in grazer-mediated defensive responses of green and red macroalgae on the south coast of South Africa - Eliecer Díaz; Christine Güldenzoph; Markus Molis; Christopher McQuaid; Martin Wahl (Marine Biology, 2006)

Culture of Calu-3 Cells at the Air Interface Provides a Representative Model of the Airway Epithelial Barrier - Christopher I. Grainger; Leona L. Greenwell; David J. Lockley; Gary P. Martin; Ben Forbes (Pharmaceutical Research, 2006)

Gaps and Mismatches between Global Conservation Priorities and Spending - BENJAMIN S. HALPERN; CHRISTOPHER R. PYKE; HELEN E. FOX; J. CHRIS HANEY; MARTIN A. SCHLAEPFER; PATRICIA ZARADIC (Conservation Biology, 2006)
Several international conservation organizations have recently produced global priority maps to guide conservation activities and spending in their own and other conservation organizations. Surprisingly, it is not possible to directly evaluate the relationship between priorities and spending within a given organization because none of the organizations with global priority models tracks how they spend their money relative to their priorities. We were able, however, to evaluate the spending patterns of five other large biodiversity conservation organizations without their own published global priority models and investigate the potential influence of priority models on this spending. On average, countries with priority areas received greater conservation investment; global prioritization systems, however, explained between only 2 and 32% of the US$1.5 billion spent in 2002, depending on whether the United States was removed from analyses and whether conservation spending was adjusted by the per capita gross domestic product within each country. We also found little overlap in the spending patterns of the five conservation organizations evaluated, suggesting that informal coordination or segregation of effort may be occurring. Our results also highlight a number of potential gaps and mismatches in how limited conservation funds are spent and provide the first audit of global conservation spending patterns. More explicit presentation of conservation priorities by organizations currently without priority models and better tracking of spending by those with published priorities are clearly needed to help make future conservation activities as efficient as possible.

Genetic mapping of expressed sequences in onion and in silico comparisons with rice show scant colinearity - William J. Martin; John McCallum; Masayoshi Shigyo; Jernej Jakse; Joseph C. Kuhl; Naoko Yamane; Meeghan Pither-Joyce; Ali Fuat Gokce; Kenneth C. Sink; Christopher D. Town; Michael J. Havey (Molecular Genetics and Genomics, 2005)

Effects of the mGluR2/3 agonist LY354740 on computerized tasks of attention and working memory in marmoset monkeys - Simona Spinelli; Theresa Ballard; Silvia Gatti-McArthur; Grayson J. Richards; Martin Kapps; Thomas Woltering; Jurgen Wichmann; Heinz Stadler; Joram Feldon; Christopher R. Pryce (Psychopharmacology, 2005)

Imaging glial cell activation with [ 11 C]- R -PK11195 in patients with AIDS - Dima A Hammoud; Christopher J Endres; Ankit R Chander; Tomas R Guilarte; Dean F Wong; Ned C Sacktor; Justin C McArthur; Martin G Pomper (Journal of NeuroVirology, 2005)

Coarse Woody Debris in Managed Central Hardwood Forests of Indiana, USA - Michael A. Jenkins; Christopher R. Webster; George R. Parker; Martin A. Spetich (Forest Science, 2004)
We evaluated the volume of down deadwood (DDW) and the basal area of standing deadwood (SDW) from a chronosequence of 110 silvicultural openings and 34 mature stands (72–105 years old) across three Ecological Landtype Phases (ELTP; wet-mesic bottomlands, mesic slopes, and dry-mesic slopes) in southern Indiana, USA. The volume of DDW decreased with increasing opening age and was lower in clearcuts than in group-selection openings. Openings on mesic slopes and bottoms contained greater volumes of DDW than openings on dry-mesic slopes. Regardless of age and ELTP, openings contained low volumes of highly decayed DDW. The volume of small-diameter DDW decreased rapidly with increasing stand age across all three ELTPs. Mature stands contained low total volumes of DDW (maximum of 22.4 ± 5.1 m3 ha−1) and low volumes of both highly decayed and large-diameter DDW. Most of the dead trees in silvicultural openings were small diameter and did not contribute significantly to DDW volume. SDW basal area was very low in mature stands (maximum of 1.4 ± 0.5 m2 ha−1), suggesting that little mortality has occurred. Our results suggest that even and uneven-aged silviculture in hardwood forests have differing impacts on the volume and distribution of coarse woody debris (CWD). In addition, the mature stands that dominate forests across much of the Central Hardwood Region of the eastern United States contain relatively little CWD compared to younger and old-growth stands. FOR. SCI. 50(6):781–792.

Quantitative trait loci for steady-state platelet count in mice - Carol C. Cheung; Ian C.A. Martin; Kyall R. Zenger; Jenny A. Donald; Peter C. Thomson; Christopher Moran; Michael F. Buckley (Mammalian Genome, 2004)

Lipopolysaccharide-induced hypoactivity and behavioral tolerance development are modulated by the light-dark cycle in male and female rats - Andrew E. Franklin; Christopher G. Engeland; Martin Kavaliers; Klaus-Peter Ossenkopp (Psychopharmacology, 2003)

Tea intake and risk of colon cancer in African-Americans and Whites: North Carolina colon cancer study - Dora Il'yasova; Christopher Martin; Robert S. Sandler (Cancer Causes & Control, 2003)

Pharmacokinetic Model to Describe the Lymphatic Absorption of r-metHu-Leptin After Subcutaneous Injection to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Maria Brumm; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2003)

Preparation of budesonide and budesonide-PLA microparticles using supercritical fluid precipitation technology - Todd M. Martin; Nagesh Bandi; Ryan Shulz; Christopher B. Roberts; Uday B. Kompella (AAPS PharmSciTech, 2002)

Effects of acute and repeated systemic administration of ketamine on prefrontal acetylcholine release and sustained attention performance in rats - Christopher Nelson; Joshua Burk; John Bruno; Martin Sarter (Psychopharmacology, 2002)

1H NMR investigations of the molecular nature of low-molecular-mass calcium ions in biofluids - Christopher J. Silwood; Martin Grootveld; Edward Lynch (JBIC Journal of Biological Inorganic Chemistry, 2002)

The importance of cholesterol in maintenance of P-glycoprotein activity and its membrane perturbing influence - Alice Rothnie; Daniel Theron; Loredana Soceneantu; Catherine Martin; Mounir Traikia; Georgina Berridge; Christopher F. Higgins; Philippe F. Devaux; Richard Callaghan (European Biophysics Journal, 2001)

Calcitonin gene-related peptide is not essential for the development of pressure overload-induced hypertrophy in vivo - Martin E. Young; Kristen A. Okerberg; Christopher R. Wilson; Dario A. Deferrari; Jun Ying; Patrick Guthrie; Peter Razeghi; Fred J. Clubb; Heinrich Taegtmeyer (Molecular and Cellular Biochemistry, 2001)

Improved incidental memory with nicotine after semantic processing, but not after phonological processing - David M. Warburton; Abigail Skinner; Christopher D. Martin (Psychopharmacology, 2001)

Repeated pretreatment with amphetamine sensitizes increases in cortical acetylcholine release - Christopher L. Nelson; Martin Sarter; John P. Bruno (Psychopharmacology, 2000)

Crystallization of Lactose from Carbopol Gels - Xian Ming Zeng; Gary P. Martin; Christopher Marriott; John Pritchard (Pharmaceutical Research, 2000)

The effects of an oral multivitamin combination with calcium, magnesium, and zinc on psychological well-being in healthy young male volunteers: a double-blind placebo-controlled trial - Douglas Carroll; Christopher Ring; Martin Suter; Gonneke Willemsen (Psychopharmacology, 2000)

The arabinose kinase, ARA1, gene of Arabidopsis is a novel member of the galactose kinase gene family - Sarah Sherson; Isabelle Gy; Jonathan Medd; Renate Schmidt; Caroline Dean; Martin Kreis; Alain Lecharny; Christopher Cobbett (Plant Molecular Biology, 1999)

Retroviral gene transfer for the assignment of Fanconi anemia (FA) patients to a FA complementation group - Kai-Ling Fu; Peter C. Thuß; Tadahiro Fujino; Martin Digweed; Johnson M. Liu; Christopher E. Walsh (Human Genetics, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

A clinical evaluation of risperidone in the treatment of schizophrenia: a 10-week, open-label, multicenter trial - D. V. Jeste; Mark Klausner; Martin Brecher; Christopher Clyde; Robert Jones (Psychopharmacology, 1997)

Normotensive blood pressure in mice with a disrupted renin Ren-1d gene - F. Bertaux; William H. Colledge; Stuart E. Smith; Martin Evans; Nilesh J. Samani; Christopher C.J. Miller (Transgenic Research, 1997)

Specific impedance of canine blood - James J. Ackmann; Martin A. Seitz; Christopher A. Dawson; Lawrence L. Hause (Annals of Biomedical Engineering, 1995)